Tungsten carbide alloy filament, preparation method thereof and heating device

By forming an appropriate carbonization layer on the tungsten matrix and adding rare earth elements, tungsten carbide alloy filaments were designed, which solved the problem of insufficient radioactive pollution and stable emission capacity of existing tungsten thorium filaments, and achieved stability comparable to traditional thorium tungsten filaments The launch capability is also avoided by radioactive contamination.

CN119457085APending Publication Date: 2025-02-18XIAMEN HONGLU TUNGSTEN MOLYBDENUM IND CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411430126.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-25
Filing Date
2024-10-14
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing tungsten and thorium filaments have problems with poor radioactive contamination and poor stable emission capabilities, and traditional thorium-free tungsten filaments lack stable emission capabilities.

Method used

Tungsten carbide alloy filament is used, which includes a matrix and a carbide layer attached to the outer surface of the matrix. The grain width of the carbide layer is between 1.0 μm and 15.0 μm. The components of the matrix and carbide layer include tungsten, carbon, oxygen and rare earths. Elements, through the structural design of the carbonized layer and the combination of rare earth elements, improve the stable emission ability of the material.

Benefits of technology

Without adding thorium, tungsten carbide alloy filaments can achieve the stable emission ability of traditional thorium tungsten filaments, solving the problem of poor stable emission ability of thorium-free tungsten filaments and avoiding radioactive contamination.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119457085A_ABST
    Figure CN119457085A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of filament cathode materials, in particular to a tungsten carbide alloy filament, a preparation method thereof and a heating device. The tungsten carbide alloy filament comprises a base body and a carbonization layer attached to the outer surface of the base body. The grain width of the carbonized layer is 1.0 [mu] m to 15.0 [mu] m; the components of the matrix and the carbonized layer comprise a tungsten element, a carbon element, an oxygen element and an M element; the M element is selected from one or a combination of more of La, Y, Sc, Nd, Sm, Lu, Ce, Gd, Tb, Dy, Ho, Pr, Er, Tm, Yb, Eu, Hf and Zr; wherein the component of the tungsten carbide alloy filament does not contain a thorium element. The emission stability of the tungsten alloy lamp filament is improved, the stable emission capability of a traditional thorium tungsten lamp filament can be achieved under the condition that no thorium element is added, the problem that an existing tungsten lamp filament without thorium is poor in stable emission capability is solved, and the problem of radioactive contamination of the traditional thorium tungsten lamp filament is solved.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application claims the priority of the Chinese patent application filed with the China Patent Office on October 25, 2023, with application number 2023113863234 and invention name “A tungsten carbide alloy filament, its preparation method, and heating device”, the entire contents of which are incorporated by reference in this application. Technical Field

[0002] The present application relates to the technical field of filament cathode materials, and in particular to a tungsten carbide alloy filament and a preparation method and a heating device thereof. Background Art

[0003] The filament cathode is the electron emitter and is widely used in the field of microwave oven magnetrons. The performance of the filament cathode has a great influence on the working characteristics and life of the magnetron and is regarded as the heart of the magnetron. Existing filament materials are mainly made of tungsten-thorium oxide materials or tungsten-rare earth oxides, for example:

[0004] The Chinese invention patent with application number CN201010299139 and publication date April 3, 2013, discloses a method for doping powder for magnetron coils. The process of the invention includes steps such as doping, stirring, and steam drying. It is characterized in that a neutralizing additive ammonia NH3·H2O solution is added to the thorium nitrate solution, and the prepared mixed solution is evenly sprayed onto the surface of the blue tungsten WO2.9 placed in the doping pot and stirred. The doping pot is evacuated and heated with water, while stirring while heating. In a vacuum state, the powder is dried by steam heating, and finally a doped tungsten-thorium oxide powder with uniform doping and low impurity content is obtained;

[0005] The invention patent (application number CN201010299139) adds thorium oxide to pure tungsten, and the service life of the magnetron coil material can reach more than 1000 hours of continuous operation. However, the cathode product made of this composite material has a high brittle-ductile transition temperature and is difficult to process and form, which can easily lead to the magnetron cathode breaking during production and transportation. In addition, the recrystallization temperature is low, and the magnetron coil will undergo abnormal recrystallization growth during the carbonization process, and often break during use and transportation, causing the magnetron to fail. At the same time, thorium is a radioactive element. Using thorium as the main added raw material will pollute the environment during smelting, production, transportation and use, and the final product made will also have potential adverse effects on the health of those who come into contact with it.

[0006] The Chinese invention patent with application number CN201410073749.9 and publication date June 11, 2014, discloses a non-radiative multi-component composite tungsten cathode material for microwave oven magnetron and its preparation process. The tungsten cathode material contains lanthanum oxide, zirconium oxide, yttrium oxide, lutetium oxide, rhenium and tungsten, wherein each rare earth oxide accounts for 0.5% to 1.5% of the mass percentage of the tungsten electrode material, the total amount of rare earth oxides accounts for 2% to 3% of the mass percentage of the tungsten electrode material, the alloy element rhenium accounts for 1% to 4% of the mass percentage of the tungsten electrode material, and the rest is tungsten. The preparation method of the non-radiative multi-component composite rare earth tungsten alloy electrode material for microwave oven magnetron includes solution preparation, drying, reduction, acid washing, cold isostatic pressing, sintering, vertical melting, medium frequency induction annealing, pressure processing, winding and mechanical straightening.

[0007] Regarding this invention patent (application number CN201410073749.9), some peers added multi-rare earth oxides into the tungsten matrix to avoid thorium radiation. This material has a strong instantaneous emission capability, but a weak stable emission capability. Its service life is far from the life standard of thorium tungsten magnetron coils, and is generally only a few dozen hours. In addition, the use of metallic rhenium is expensive, which is not conducive to industry promotion and use.

[0008] In summary, the traditional tungsten-thorium filament is radioactive, which not only pollutes the environment, but also has potential adverse effects on the health of the people who come into contact with it. In addition, the existing filaments that do not use thorium addition have the problem of poor stable emission ability. How to solve the above problems is exactly the difficulty that technicians in this field are committed to overcoming. Summary of the invention

[0009] In order to solve the problems existing in the above-mentioned prior art: the traditional tungsten-thorium filament is radioactive, which not only pollutes the environment, but also has potential adverse effects on the health of the contacted people in the final product. In addition, the existing filaments that do not use thorium addition have the defect of poor stable emission ability. This application provides a tungsten carbide alloy filament, and the specific technical solution is as follows:

[0010] The tungsten carbide alloy filament comprises a substrate and a carbide layer attached to the outer surface of the substrate; the grain width of the carbide layer is 1.0 μm to 15.0 μm; the components of the substrate and the carbide layer both contain tungsten, carbon, oxygen and M; the M element is selected from one or more combinations of La, Y, Sc, Nd, Sm, Lu, Ce, Gd, Tb, Dy, Ho, Pr, Er, Tm, Yb, Eu, Hf and Zr; wherein the components of the tungsten carbide alloy filament do not contain thorium.

[0011] In some embodiments, the M element in the carbonized layer exists in the form of an oxide, the particle size of the M oxide particles is 10 nm to 1000 nm, and the carbon element exists in the form of a carbide.

[0012] In some embodiments, a plurality of second channels are distributed on the carbonized layer to form a radially stacked layered structure on the cross section of the filament; a plurality of first channels are distributed on the carbonized layer, and at least some of the first channels are cross-arranged with the second channels to divide the stacked layered structure into a plurality of block structures.

[0013] In some embodiments, a plurality of first channels are distributed on the carbide layer; at least part of the first channels are distributed radially along the cross-section of the filament; and / or at least part of the first channels point to the center of the cross-section of the filament; a plurality of second channels are distributed on the carbide layer; at least part of the second channels are distributed circumferentially along the cross-section of the tungsten alloy filament; wherein at least part of the second channels are cross-arranged with the first channels.

[0014] In some embodiments, the composition of the carbonized layer includes W 2 C and WC; W 2 The weight ratio of C to WC is (60-100):(0-40).

[0015] In some embodiments, in the matrix, the M element exists in the form of an oxide, and the carbon element exists in the form of a carbide or a single carbon substance.

[0016] In some embodiments, the matrix comprises the following components: 0.0005-0.3 wt % carbon element, 0.25-2.6 wt % M element, 0.05-0.5 wt % oxygen element, and the balance is tungsten element and inevitable impurities.

[0017] In some embodiments, among the components of the matrix, the M element exists in the form of an oxide, and the carbon element exists in the form of a carbide or a carbon element; the oxide of M is selected from one or more combinations of lanthanum oxide, yttrium oxide, scandium oxide, neodymium oxide, samarium oxide, lutetium oxide, cerium oxide, gadolinium oxide, terbium oxide, dysprosium oxide, holmium oxide, praseodymium oxide, erbium oxide, hafnium oxide, and zirconium oxide; the carbide is selected from one or more combinations of lanthanum carbide, zirconium carbide, yttrium carbide, hafnium carbide, and tungsten carbide.

[0018] In some embodiments, the components of the matrix further include a metal element T; T is selected from at least one of K, Re, Mo, Fe, and Co.

[0019] In some embodiments, the mass content of Re is less than 1000 ppm.

[0020] In some embodiments, the wire diameter of the tungsten carbide alloy filament is 800 μm or less.

[0021] In some embodiments, the operating temperature is 1100°C to 1500°C.

[0022] In some embodiments, the tungsten carbide alloy filament is a spiral structure with a pitch of 0.800-1.800 mm, a length of 10.00-16.00 mm, and an outer diameter of 3.00-6.00 mm.

[0023] In some embodiments, the tungsten carbide alloy filament is a spiral structure, and the thickness of the carbide layer of at least one spiral turn reaches 30 μm to 90 μm.

[0024] The present application provides a method for preparing the tungsten carbide alloy filament as described above, which comprises the following steps:

[0025] S1. Doping and powder making: a finished powder raw material is obtained by sequentially performing a doping process, a reduction process and a powder making process; wherein the doping process is solid-liquid doping or solid-solid doping;

[0026] S2. Powder pressing: using isostatic pressing to press the finished powder raw material into a compact, and pre-sintering the compact at a low temperature in a hydrogen atmosphere to obtain a pre-sintered blank;

[0027] S3, high temperature sintering: high temperature sintering the pre-sintered billet to obtain a sintered billet;

[0028] S4, pressure processing: thinning the sintered billet into a tungsten alloy wire with a certain diameter; wherein, oxidation annealing is performed during the thinning process;

[0029] S5. Cleaning: Clean the tungsten alloy wire into tungsten alloy white wire;

[0030] S6, Winding: Winding the tungsten alloy white wire into a spring-like filament structure;

[0031] S7, cathode assembly: assembling the spring-shaped filament structure and components, ceramics, and lead parts into a cathode structure through heat treatment;

[0032] S8, welding: welding the filament structure in the cathode structure to the component end cap;

[0033] S9. Carbonization: Carbonize the welded cathode structure.

[0034] The present application also provides a heating device, which includes the above tungsten carbide alloy filament.

[0035] In some embodiments, the heating curve of the high temperature sintering step is: heating from room temperature to A1, the heating time H1 is (5-8) h, A1 is (950-1250) ° C; keeping at A1 for H2 hours, H2 is (1-3); heating from A1 to A2, the heating time is H3, H3 is (1.5-2.5) h, A2 is (1300-1500) ° C; keeping at A2 for H4 hours, H4 is (2.5-4 .5); heating from A2 to A3, the heating time is H5, H5 is (1~3)h, A3 is (1700~1900)℃; keeping warm at A3 for H6 hours, H6 is (1~3); heating from A3 to A4, the heating time is H7, H7 is (1~3)h, A4 is (2050~2250)℃; keeping warm at A4 for H8 hours, H8 is (5~10); naturally cooling from A4 to obtain sintered billets.

[0036] In some embodiments, the process of the pressure processing step is: the sintered billet is refined to an intermediate specification wire with a diameter of 1.5 to 3.5 mm; and then the intermediate specification wire is oxidized and annealed at (1200 to 1500) ° C at an annealing speed of (3 to 10) m / min to obtain tungsten alloy wire.

[0037] Based on the above, compared with the prior art, this application has the following advantages:

[0038] The tungsten carbide alloy material of the present application is designed with a carbide layer and a rare earth element component, and the rare earth atoms stably migrate outward to supplement the rare earth element evaporated from the surface, thereby improving the emission stability of the material. Without adding thorium elements, it can also achieve the stable emission capability of traditional thorium tungsten filaments, solve the problem of poor stable emission capability of existing thorium-free tungsten filaments, and does not have the radioactive pollution problem of traditional thorium tungsten filaments.

[0039] Other features and beneficial effects of the present application will be described in the subsequent description, and partly become apparent from the description, or understood by practicing the present application. The purpose and other beneficial effects of the present application can be realized and obtained by the structures specifically pointed out in the description, claims and drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, a brief introduction will be given below to the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0041] Figure 1 A schematic diagram of a portion of the structure of the tungsten alloy filament provided in this application;

[0042] Figure 2 A schematic diagram of the cross-section of a tungsten alloy filament provided in this application;

[0043] Figure 3 A schematic diagram of the longitudinal section of the tungsten alloy filament provided in this application;

[0044] Figure 4 for Figure 2 The enlarged view of point A in the middle;

[0045] Figure 5 The metallographic image of Comparative Example 1 provided in this application at 44% FC;

[0046] Figure 6 The metallographic image of Comparative Example 1 provided in this application at 46% FC;

[0047] Figure 7 The metallographic image of Comparative Example 1 provided in this application at 48% FC;

[0048] Figure 8 The metallographic image of Comparative Example 1 provided in this application at 50% FC;

[0049] Fig. 9 The metallographic image of Example 1 provided in this application at 48% FC;

[0050] Fig.10 The metallographic image of Example 1 provided in this application at 50% FC;

[0051] Fig.11 The metallographic image of Example 1 provided in this application at 52% FC;

[0052] Fig.12 A schematic diagram of the crystal structure of Comparative Example 1 provided in this application;

[0053] Fig.13 A schematic diagram of the crystal structure of Example 1 provided in this application;

[0054] Fig.14 A diagram showing the channel distribution of the cross section of Example 1 provided in the present application;

[0055] Fig.15 A diagram showing the channel distribution of the longitudinal section of Example 1 provided in the present application;

[0056] Fig.16 A diagram showing the channel distribution of the cross section of Comparative Example 1 provided in the present application;

[0057] Fig.17 A diagram showing the channel distribution of the cross section of Comparative Example 4 provided in the present application;

[0058] Fig.18 A diagram showing the channel distribution in the longitudinal section of Comparative Example 4 provided in the present application;

[0059] Fig.19 Schematic diagram of the overall structure of the tungsten alloy filament provided in this application;

[0060] Fig. 20 A schematic diagram of the process flow for preparing a heating device from tungsten alloy wire provided in this application;

[0061] Fig.21 This is the conversion relationship diagram between FC% and degrees Celsius;

[0062] Fig. 22 A partial structural schematic diagram of the cross section of the tungsten alloy filament provided in this application.

[0063] Reference numerals:

[0064] 100 substrate 200 carbonized layer 210 channel

[0065] 220 outer edge of the filament 211 first channel 212 second channel DETAILED DESCRIPTION

[0066] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments; the technical features designed in different implementation modes of the present application described below can be combined with each other as long as they do not conflict with each other; based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0067] In the description of this application, it should be noted that all terms used in this application (including technical terms and scientific terms) have the same meaning as those commonly understood by ordinary technicians in the field to which this application belongs, and cannot be understood as limiting this application; it should be further understood that the terms used in this application should be understood to have the same meaning as these terms in the context of this specification and the relevant field, and should not be understood in an idealized or overly formal sense, unless explicitly defined in this application.

[0068] The present application provides a tungsten carbide alloy material, and its technical solution is as follows:

[0069] The tungsten carbide alloy material comprises a substrate and a carbide layer attached to the outer surface of the substrate; the grain width of the carbide layer is between 1.0 μm and 15.0 μm; the components of the substrate and the carbide layer both contain tungsten, carbon, oxygen and M element, and the M element is selected from one or more combinations of La, Y, Sc, Nd, Sm, Lu, Ce, Gd, Tb, Dy, Ho, Pr, Er, Tm, Yb, Eu, Hf and Zr; wherein the components of the tungsten carbide alloy filament do not contain thorium.

[0070] 1. Preferred structural features and phase composition features of the carbonized layer 200:

[0071] (1) The M element in the carbide layer exists in the form of oxide, and the carbon element exists in the form of carbide. The particle size of the M oxide particles is 10nm to 1000nm.

[0072] (2) Figure 1-4 As shown, a plurality of first channels 211 are distributed on the carbonized layer 200; at least part of the first channels 211 are distributed along the radial direction of the filament cross section; and / or at least part of the first channels 211 point to the center of the filament cross section.

[0073] (3) Figure 4 and Fig. 22 As shown, a plurality of channels 210 are distributed on the carbide layer 200, and the channels 210 include a first channel 211 and a plurality of second channels 212; at least a portion of the first channels 211 are distributed radially along the cross section of the tungsten alloy filament; and / or, at least a portion of the first channels 211 point to the center of the cross section of the tungsten alloy filament; and at least a portion of the second channels 212 are distributed circumferentially along the cross section of the tungsten alloy filament, wherein at least a portion of the second channels 212 are cross-arranged with the first channels 211, so that the cross section of the carbide layer 200 is in a block-like shape.

[0074] Specifically, the present application controls the structure of the carbide layer 200: its grain size is controlled within a certain small range (grain width is 1.0 μm to 15.0 μm) to form a large number of first channels 211 and second channels 212, thereby forming a layer block structure, and cooperates with the rare earth components in the tungsten alloy filament to achieve a stable emission effect. The specific mechanism is:

[0075] like Fig. 22As shown, the second channel 212 divides the carbonized layer 200 into a layered structure stacked in a radial direction, and then divides the carbonized layer 200 into a block structure through the first channel 211 designed to cross it, so that the carbonized layer 200 forms a layer block. Compared with other structural distributions, for example, the first channel 211 divides the carbide layer 200 into a block structure, the second channel 212 divides the carbide layer 200 into a radially stacked layer structure, the second channel 212 and the first channel 211 are not designed to cross, and the carbide layer 200 forms two clearly divided areas, one area is a block structure, and the other area is a layered structure; the grain control of the carbide layer 200 of the present application makes its cross section a layered block design, which has the advantages of: the radial or quasi-vertical distribution design of the first channel 211 is conducive to the outward migration of rare earth atoms of the M element, and the layered structure in the carbide layer 200 separated by the second channel 212 is where the oxides of M are distributed. The second channel 212 is combined with the first channel 211 (vertical channel 210) to form a layered block of the carbide layer 200, which can effectively control the migration speed of the oxides of M to the filament surface (i.e., the outer surface of the carbide layer 200), thereby improving the stable emission ability of the tungsten carbide alloy.

[0076] It should be noted that:

[0077] like Figure 1 The filament structure, Figure 2 The cross section of the filament and Figure 3 As shown in the longitudinal section of the filament, for the “radial distribution along the cross section of the filament”, “at least part of the first channel 211 points to the center of the cross section of the filament”. For the radial distribution and the center of the circle: it means that the end point of the first channel 211 close to the substrate 100 and the end point close to the edge of the filament are connected to form a first straight line, and the angle between the first straight line and the tangent line of the intersection of the outer edge 220 of the filament is (60-90)°.

[0078] like Fig. 22 As shown, for the “circumferential distribution along the cross section of the tungsten alloy filament” in this article, the circumferential distribution means connecting the end points of the second channel 212 into a second straight line, and the angle between the second straight line and the straight line where the filament radial direction is located is (-45 to +45) degrees.

[0079] In the present application, the first channel 211 and the outer edge 220 of the filament (i.e., the outer edge of the carbonized layer 200) are quasi-vertically and quasi-radially distributed. The radial or quasi-vertical distribution design of the first channel 211 is beneficial to the outward migration of M element atoms, but it does not mean that the first channel 211 is a straight line structure, nor does it mean that the two end points of the first channel 211 need to pass through to the outer edge of the substrate 100 and the carbonized layer 200 (i.e., the outer edge 220 of the filament).

[0080] In the present application, the second channel 212 is distributed along the annular direction or is cross-arranged with the first channel 211, which does not mean that the second channel 212 is a standard arc structure, and does not mean that the second channel 212 is continuously connected to run through the entire outer ring. It can be a quasi-annular distribution composed of multiple sections of second channels 212 separated from each other, or a cross-distribution of multiple sections of second channels 212 separated from each other and the first channel 211, so that the carbonized layer 200 is divided into a layered structure stacked along the radial direction.

[0081] (3) The tungsten carbide alloy filament has a spiral structure, and the thickness of the carbide layer of at least one spiral turn is 30 μm to 90 μm, preferably 35 to 45 μm, 50 to 90 μm, for example 60 μm, 70 μm, 80 μm.

[0082] (4) The components of the carbonized layer 200 include W2C and WC; W 2 The weight ratio of C to WC is (60-100):(0-40).

[0083] 2. Preferred component characteristics for tungsten carbide alloy materials:

[0084] (1) In the matrix, the M element exists in the form of oxides, and the carbon element exists in the form of carbides or carbon elements.

[0085] The present application adds one or more oxides of M and carbides or carbon elements. Since the oxides of M and carbides in the tungsten matrix react at high temperatures, for example, lanthanum oxide reacts with tungsten carbide to generate lanthanum atoms, and the size of the generated lanthanum atoms is much smaller than that of lanthanum oxide particles, the migration and diffusion speed of lanthanum atoms in the tungsten matrix will be very fast, thereby increasing the diffusion speed of M metal atoms. In summary, the present application combines the oxides of M with carbides or carbon elements, and can achieve the same or even higher electron emission capability as thoriated tungsten at a lower operating voltage (excitation temperature) than thoriated tungsten filaments, and it is easier to ensure the balance between the loss and migration of rare earth atoms in the carbide layer of the filament, thereby ensuring the stability of the electron emission of the filament.

[0086] (2) The matrix of the tungsten carbide alloy filament comprises the following components: 0.0005-0.3wt% carbon element, 0.25-2.6wt% M element, 0.05-0.5wt% oxygen element, and the balance is tungsten element and inevitable impurities. Preferably, the matrix of the tungsten carbide alloy filament consists of the following components: 0.0005-0.3wt% carbon element, 0.25-2.6wt% M element, 0.05-0.5wt% oxygen element, and the balance is tungsten element and inevitable impurities.

[0087] Among them, the M element can be 1.28-2.6wt%, and the tungsten alloy filament made of the tungsten alloy material with this composition ratio is better for use in microwave ovens <800W. The M element can be 0.25-1.28wt%, and the tungsten alloy filament made of the tungsten alloy material with this composition ratio is better for use in microwave ovens >800W. Furthermore, the M element can be 0.25-0.86wt%, and the tungsten alloy filament made of the tungsten alloy material with this composition ratio is better for use in microwave ovens >1000W.

[0088] Wherein, preferably, M exists in the tungsten alloy material in the form of an oxide, and the oxide of M is selected from one or more combinations of lanthanum oxide, yttrium oxide, scandium oxide, neodymium oxide, samarium oxide, lutetium oxide, cerium oxide, gadolinium oxide, terbium oxide, dysprosium oxide, holmium oxide, praseodymium oxide, erbium oxide, hafnium oxide, and zirconium oxide; carbon element exists in the tungsten alloy material in the form of carbide or carbon element, and the carbide is selected from one or more combinations of lanthanum carbide, zirconium carbide, yttrium carbide, hafnium carbide, and tungsten carbide. For example, the oxide of M can be selected from lanthanum oxide, or a combination of lanthanum oxide and yttrium oxide, or a combination of lanthanum oxide and zirconium oxide, or a combination of lanthanum oxide and scandium oxide, or a combination of lanthanum oxide and hafnium oxide, etc.

[0089] Preferably, the matrix of the tungsten alloy material further comprises T, where T is a solid solution metal element or a dispersed metal element, and T is selected from at least one of K, Re, Mo, Fe, and Co. Further preferably, the mass content of Re is less than 1000 ppm.

[0090] It should be noted that:

[0091] “La, Y, Sc, Nd, Sm, Lu, Ce, Gd, Tb, Dy, Ho, Pr, Er, Tm, Yb, Eu, Hf, Zr” in the text are element symbols in the periodic table, representing the metal elements lanthanum, yttrium, scandium, neodymium, samarium, lutetium, cerium, gadolinium, terbium, dysprosium, holmium, praseodymium, erbium, thulium, ytterbium, europium, hafnium and zirconium in the periodic table respectively; “K, Re, Mo, Fe, Co” in the text are element symbols in the periodic table, representing the metal elements potassium, rhenium, molybdenum, iron and cobalt in the periodic table respectively; W is the symbol of tungsten in the periodic table; C is the symbol of carbon in the periodic table; in addition, “M” and “T” are only reference symbols and do not represent elements in the periodic table and are only used for reference.

[0092] 3. The wire diameter of tungsten carbide alloy filament can reach 800μm and below:

[0093] In the pressure processing process, the tungsten alloy material provided by the present application has good processing performance and can be processed into wires with fine wire diameter specifications (i.e., fine wire diameter tungsten alloy wires), and the wire diameter tolerance can be controlled within a very small range.

[0094] Furthermore, the wire diameter can be 600 μm or less, 550 μm or less, or even 500 μm or less. The wire diameter can be 450-550 μm, such as 470 μm, 490 μm, 500 μm, 520 μm, etc., or 700-800 μm, such as 750 μm, 760 μm, 780 μm, etc.

[0095] 4. The tungsten carbide alloy filament has a spiral structure during actual use. The preferred structural features of the spiral structure of the tungsten alloy filament are as follows:

[0096] 4.1 Turn control: Fig.19 The structural schematic diagram of the tungsten alloy filament shown in the figure preferably has a number of turns of (9.5 to 13) turns, a control tolerance of ±0.125, and a statistical CPK>1.33.

[0097] The number of turns of the filament is between 9.50 and 13.00 turns. The preferred number of turns may be between 9.70 and 10.70 turns, such as 9.90 turns, 10.00 turns, 10.28 turns, 10.5 turns, etc.; it may also be between 10.70 and 11.70 turns, such as 11.00 turns, 11.20 turns, 11.5 turns, etc.; it may also be between 11.80 and 13.00 turns, such as 12.00 turns, 12.20 turns, 12.5 turns, etc.

[0098] 4.2 Pitch uniformity, the tolerance of the tungsten alloy filament pitch L1 is ±0.02, and the statistical CPK>1.33; wherein, the tungsten alloy filament pitch L1 is Fig.19 In the implementation process, those skilled in the art can use a dedicated wire winding device to make the filament pitch uniform so that the heating device can emit electrons more stably.

[0099] It should be noted that the number of filament turns is related to the filament length L and the pitch L 1 Related, filament length L = (filament turns - 1) * L 1 .

[0100] 4.3 Pitch size: the pitch L1 of the tungsten alloy filament is 0.800~1.800mm, and the preferred pitch L 1 , can be 1.000-1.150mm, such as 1.018mm, 1.044mm, 1.135mm, etc., can also be 1.230mm-1.330mm, such as 1.240mm, 1.290mm, etc., can also be 1.400mm-1.600mm, such as 1.470mm, 1.500mm, etc.;

[0101] 3.4 Length: The length L of the filament is between 10.00 and 16.00 mm, and the preferred length L can be between 10.50 and 12.00 mm, such as 11.00 mm, 11.20 mm, 11.70 mm, etc., or can be between 12.50 and 14.00 mm, such as 12.83 mm, 13.40 mm, 13.55 mm, etc.;

[0102] The outer diameter of the filament Φ 1 In the range of 3.00~6.00mm, the preferred outer diameter Φ 1 , it can be 3.50~4.50mm, such as 3.70mm, 3.80mm, 3.90mm, 3.92mm, 4.00mm, etc., or it can be 5.00~6.00mm, such as 5.20mm, 5.48mm, 5.60mm, etc.

[0103] Among them, the present application also provides the following preferred implementation schemes for preparing tungsten alloy wire (finished product before carbonization, steps 1-6), carbide tungsten alloy filament (steps 1-9), and prepare a heating device containing tungsten alloy filament (steps 1-12):

[0104] It includes the following steps:

[0105] Step 1, obtaining a finished powder raw material through a doping process, a reduction process and a powder making process in sequence; wherein the doping process is solid-liquid doping or solid-solid doping;

[0106] Step 2, powder pressing: using isostatic pressing to press powders of different particle sizes into green compacts, and pre-sintering the green compacts at low temperature in a hydrogen atmosphere to increase the green compact strength; wherein the powders are pressed into green compacts with a unit weight of 1.5 to 5.0 kg at a pressure of 160 to 240 MPa;

[0107] Step 3: High temperature sintering: high temperature sintering is used to obtain a density of 17.5-18.3 g / cm 3 The sintered billet is to obtain the tungsten alloy material in billet form;

[0108] The heating curve of the high temperature sintering method is:

[0109] Heating from room temperature to A1, heating time H1 is (5-8) h, A1 is (950-1250) °C;

[0110] For example, H1 is (5-7) h, (7-8) h, etc., and another example is 6 h, 7.5 h, etc.; A1 is (950-1050) ° C, (1050-1250) ° C, etc., and another example is 1000 ° C, 1100 ° C, etc.;

[0111] Keep warm at A1 for H2 hours, H2 is (1~3);

[0112] For example, H2 is (1-2)h, (2-3)h, etc., and another example is 1.5h, 2.5h, etc.;

[0113] From A1 to A2, the heating time is H3, H3 is (1.5~2.5)h, A2 is (1300~1500)℃;

[0114] For example, H3 is (1.5-2.0) h, (2.0-2.5) h, etc., and another example is 1.5 h, 2.0 h, 2.4 h, etc.; A2 is (1300-1400X) ° C, (1400-1500) ° C, etc., and another example is 1350 ° C, 150 ° C, etc.;

[0115] Keep warm at A2 for H4 hours, H4 is (2.5~4.5);

[0116] For example, H4 is (2.5-3.0)h, (3.0-4.0)h, etc., and another example is 2.8h, 3.5h, etc.;

[0117] From A2 to A3, the heating time is H5, H5 is (1-3) h, A3 is (1700-1900) °C;

[0118] For example, H5 is (1-2)h, (2-3)h, etc., and another example is 1.6h, 2.0h, 2.5h, etc.; A3 is (1700-1800)℃, (1800-1900)℃, etc., and another example is 1750℃, 1850℃, etc.;

[0119] Keep warm at A3 for H6 hours, H6 is (1-3);

[0120] For example, H6 is (1-2)h, (2-3)h, etc., and another example is 1.5h, 2.5h, etc.;

[0121] From A3 to A4, the heating time is H7, H7 is (1-3)h, A4 is (2050-2250)℃;

[0122] For example, H7 is (1-2)h, (2-3)h, etc., and another example is 1.5h, 2.5h, etc.; A4 is (2050-2150)℃, (2150-2250)℃, etc., and another example is 2100℃, 2200℃, etc.;

[0123] Keep warm at A4 for H8 hours, H8 is (5-10);

[0124] For example, H8 is (5-7)h, (7-10)h, etc., and another example is 6h, 8h, etc.;

[0125] It is obtained by natural cooling from A4.

[0126] Step 4: Pressure processing:

[0127] 4.1 In the pressure processing step, the tungsten alloy sintered billet obtained after sintering is refined into an intermediate specification wire with a diameter of 1.5 to 3.5 mm;

[0128] 4.2 Then, the intermediate specification wire is subjected to oxidation annealing at (1200-1500)°C, with an annealing speed of (3-10) m / min;

[0129] For example, the annealing speed is (3-7) m / min, (7-10) m / min, etc., and another example is 3 m / min, 5 m / min, 7 m / min, etc.; the oxidation annealing is (1200-1350)°C, (1350-1500)°C, etc., and another example is 1250°C, 1400°C, etc.;

[0130] 4.3 After oxidation annealing, continue to process the intermediate specification wire to the required wire diameter specification to obtain tungsten alloy wire;

[0131] Among them, multiple rotary forging and drawing methods are used for diameter reduction processing; the oxidation annealing process is carried out in the oxidation annealing equipment, and the annealing speed refers to the speed at which the wire passes through the annealing tank, which indicates the length of the wire passing through the annealing tank per unit time.

[0132] Step 5, white wire cleaning: Use electrolytic cleaning to clean the black wire into tungsten alloy white wire that can be processed into microwave oven heating device filament;

[0133] Step 6, winding: Wind the white wire into a spring-shaped filament structure for the heating device to obtain tungsten alloy wire;

[0134] Step 7, cathode assembly: assemble the spring-shaped filament structure and components, ceramics, lead pieces and other parts into a cathode structure through heat treatment;

[0135] Step 8, welding: welding the filament structure in the cathode structure to the component end cap;

[0136] Step 9, carbonization: carbonize the welded cathode structure to obtain a tungsten carbide alloy filament;

[0137] Step 10, white ball assembly: assemble the cathode structure, anode cylinder, antenna end cap and other components together;

[0138] Step 11, exhaust the white ball, evacuate it, and age it at high temperature to complete the manufacture of the black ball and activate its emission performance;

[0139] Step 12: Assemble the black ball, heat sink, magnet, tube shell, etc. to finally obtain a heating device component containing the above-mentioned tungsten carbide alloy filament, and put it into a microwave oven for use.

[0140] 1. The preferred structural features of the tungsten alloy wire before carburization (i.e. the wire obtained after pressure processing) are as follows:

[0141] 1.1 Characteristics of the initial recrystallization temperature:

[0142] The initial recrystallization temperature of the tungsten alloy wire provided by the present application is higher than that of the thoriated tungsten wire, which is 48%Fc to 56%Fc in the present application, while the thoriated tungsten wire is around 46%FC (2020°C).

[0143] The average size of 80%Fc recrystallized grains of the tungsten alloy wire provided by the present application is finer than that of the thoriated tungsten wire. The average size of 80%Fc recrystallized grains of the tungsten alloy wire provided by the present application is (1-15) μm, and the average size of 80%Fc recrystallized grains of the thoriated tungsten filament is (16-150) μm.

[0144] The above characteristics of high initial recrystallization temperature and small average size of 80% Fc recrystallized grains make the tungsten matrix structure of the filament produced by the tungsten alloy wire of the present application finer than that of the thorium tungsten filament after carburization in the magnetron, thereby making the grain width of the carbide layer of the tungsten alloy filament finer after carburization, so that the grain width of the carbide layer is controlled within the required range;

[0145] There is a carbonization process in the process of preparing tungsten alloy wire into tungsten carbide alloy. The carbonization temperature is 2000-2500℃. The original thoriated tungsten filament is carbonized at this temperature (the reason is that its initial recrystallization temperature is too low after analysis). The grain structure will show recrystallization phenomenon, and the grains are coarse, which makes the filament brittle and poor in seismic resistance after carbonization. It is very easy to break the wire during the assembly, production, transportation and subsequent use of the magnetron microwave oven. Compared with the thoriated tungsten filament, the initial recrystallization temperature of the filament material selected in this application is higher than that of the original thoriated tungsten filament, and the average size of 80% Fc recrystallized grains is smaller than that of the original thoriated tungsten filament. After the tungsten alloy wire of this application is carbonized, the filament structure is still fine-grained, and the brittleness is less than that of the traditional thoriated tungsten filament material. The tungsten alloy filament with fine grain structure has better seismic resistance than the thoriated tungsten filament. The filament breaking rate of the magnetron produced by this application is much lower than that of the magnetron produced by traditional thoriated tungsten.

[0146] Optionally, the initial recrystallization temperature of the tungsten alloy wire may be 48%-52% FC, such as 48% FC, 50% FC, 52% FC, and the like.

[0147] Optionally, the average size of 80%Fc recrystallized grains of the tungsten alloy wire can be (1-8) μm, (8-12)% μm, (12-15) μm, etc., for example, 4.0 μm, 8.5 μm, 13 μm, etc.

[0148] 1.2 The average size characteristics of the oxide particles in the tungsten alloy wire: The average size of the oxide particles in the tungsten alloy wire is (100-500) nm

[0149] The average size of the oxide particles of the tungsten alloy wire of the present application is (100-500) nm. The size of the oxide particles of the tungsten alloy wire determines the size of the oxide particles of the filament after carburization. If the oxide particles of the wire are too coarse relative to the range specified in the present application, resulting in coarse particles of the tungsten alloy filament after carburization, then during the use of the magnetron, it will be more difficult for the oxide particles of M to migrate to the surface of the filament, which will make it easier for the balance of rare earth element loss and replenishment on the surface of the filament to be broken, and the electron emission of the magnetron will be more unstable.

[0150] Optionally, the average size of the oxide particles may also be (100-300) nm, (300-500) nm, etc., for example, 200 nm, 300 nm, 450 nm, etc.

[0151] 1.3 For the above tungsten alloy wire crack detection characteristics:

[0152] The number of crack points detected by the above tungsten alloy wire is less than 5 (per 100 meters). Further, the number of crack points detected by the tungsten alloy wire can be less than 2 per 100 meters, such as 0 per 100 meters, 0.5 per 100 meters, 1 per 100 meters, and the like.

[0153] Tungsten alloy wire has fewer crack points during flaw detection, a high filament yield rate, and is not prone to wire breakage.

[0154] 2. Important control points for the preferred implementation of the method for preparing tungsten alloy wire before carburization:

[0155] The present application can obtain the above-mentioned tungsten alloy wire before carbide with the above-mentioned starting recrystallization temperature and average size characteristics of oxide particles through the preferred implementation scheme of the above-mentioned preparation method. Through the carbonization treatment of the tungsten alloy wire, a tungsten carbide alloy filament with the above-mentioned carbide layer grain width, carbide layer oxide particle size and other characteristics can be obtained. The specific process control points of the preparation method for obtaining the tungsten alloy wire before carbide are as follows:

[0156] (1) Oxidation annealing treatment of intermediate specifications:

[0157] The present application provides a specific treatment method for oxidation annealing in the above-mentioned pressure processing step, so that the initial recrystallization temperature of the tungsten alloy is controlled within the above-mentioned required range (48%Fc~56%Fc): a stress relief oxidation annealing at a temperature of 1200~1500°C is added at the middle specification of the wire of 1.5~3.5mm, so that the initial recrystallization temperature of the tungsten alloy wire is effectively controlled within 48%Fc~56%Fc; in this preparation process, if the oxidation annealing process is removed, the initial recrystallization temperature of the tungsten alloy wire exceeds 56%Fc, and the excessively high initial recrystallization temperature will be detrimental to the electron emission performance of the tungsten carbide alloy filament under the working conditions of the magnetron.

[0158] (2) By controlling the time from A1 to A2 and the sintering time at A2 (1300-1500°C) during the sintering process:

[0159] In the high-temperature sintering stage of the tungsten blank, the present application provides a sintering process, which controls the time of heating from A1 to A2 and the sintering time at A2 (1300-1500°C) in the sintering process, so that the sintering neck of the tungsten blank grows rapidly, closes the holes, and prevents the oxide particles in the holes from being squeezed into another hole from the unclosed connecting channel during the shrinkage of the sintering cavity of the billet, thereby ensuring the density of the sintered billet and controlling the size of the oxide particles of the sintered billet, thereby controlling the oxide size of the tungsten alloy wire or the filament after carbonization;

[0160] Among them, the oxide particle size distribution range of the tungsten alloy sintered billet obtained by the above sintering process is 100-2000nm, and the average size of the oxide particles is 600-1000nm, and the average size of the oxide particles of the tungsten alloy wire is (100-500)nm; optionally, the average size of the oxide particles can also be (100-300)nm, (300-500)nm, etc., for example, 200nm, 300nm, 450nm, etc.

[0161] Without the above sintering process, the oxide particle size distribution range of tungsten alloy sintered billet is 400-5000nm, and the average size of oxide particles is 1200-2000nm. The average size of oxide particles of tungsten alloy wire after further refinement is also relatively coarse (about 500-900nm).

[0162] Among them, the mechanism of the sintering process affecting the oxide size of the billet, tungsten alloy wire, and carbonized filament, as well as the effect of the oxide size of the tungsten alloy wire and carbonized filament on the performance of the filament is as follows: the reason why the oxide particle size is controlled within a smaller range is that the oxide particle size of the billet directly determines the oxide size of the tungsten alloy wire or carbonized filament. If the oxide particles of the wire are coarser, it will be more difficult for the particles to migrate to the surface of the filament during the use of the magnetron, which will make it easier to break the balance between the loss and replenishment of rare earth elements on the surface of the filament, making the magnetron electron emission more unstable.

[0163] The adjustment of sintering process affects the speed of sintering neck growth and pore closure of tungsten billet. The sintering process provided can reduce the possibility of oxide particle aggregation, thereby reducing the oxide particle size of sintered billet. The specific principle of high temperature sintering process is explained as follows:

[0164] The isostatic pressed green sheet is a dense accumulation of powders with a porosity of about 35-45%. We can simply imagine these pores as holes with multiple channels connected, and the oxide particles are evenly distributed on the inner surface of the holes. During the high-temperature sintering process, the tungsten particles bonded together form a "sintering neck". As the sintering temperature increases, the sintering neck continues to grow and blocks the channels connecting the holes, which produces isolated holes. These isolated holes will gradually become round, making the inner surface area of ​​the hole smaller, and then causing the originally similar small oxide particles to gather together to form larger oxide particles. As the high-temperature sintering proceeds, the holes shrink further through diffusion, and the oxide particles distributed on the inner surface of the holes can only further gather to form one or several larger oxide particles.

[0165] Some of the smaller holes merge with adjacent large holes due to diffusion, or shrink before the connecting hole channels are closed. The oxide particles in these small holes will be pushed to the adjacent unclosed holes, making the unclosed holes contain more oxide than other places, which in turn causes the oxide particles to be larger than other places.

[0166] The present application also provides the following embodiments and comparative examples:

[0167] The weight formula of the raw material components and the element ratio of the prepared filament material of the embodiments and comparative examples provided in this application are shown in Table 1 below:

[0168] Table 1

[0169]

[0170]

[0171] Specifically, according to the formula in Table 1, the raw material components in the embodiment and the comparative example are prepared according to the following preparation method to prepare a tungsten alloy filament and a heating device:

[0172] Example 1

[0173] 1. According to the formula in Table 1, add 5L of deionized water to a certain amount of lanthanum nitrate solution, stir for 10 minutes to fully dissolve, then add 1L of ammonia NH3·H2O solution and stir to neutralize, and evenly spray the prepared mixed solution onto the blue tungsten placed in the doping pot and stir; wherein, the volume ratio of lanthanum nitrate solution to ammonia NH3·H2O solution is 5:1;

[0174] 2. Evacuate the doping pot and heat it with water (heating temperature 80°C, vacuum degree -0.025MPa), stirring while heating;

[0175] 3. Under vacuum, the powder is dried by steam heating, the steam pressure is 0.1~0.3MPa, the vacuum degree in the pot is ≤-0.02MPa, and finally tungsten-lanthanum doped powder with uniform doping and low impurity content is obtained;

[0176] 4. Reduce the tungsten-lanthanum doped powder into tungsten-lanthanum powder of suitable particle size in a reduction furnace with four temperature zones at 650°C, 750°C, 850°C and 900°C;

[0177] 5. Put the obtained tungsten-lanthanum powder and tungsten carbide into a high-speed powder mixer for solid-solid powder mixing for 2 hours, and sieve to obtain mixed tungsten-lanthanum alloy powder;

[0178] 6. The powder with a particle size of 1.5 μm was pressed into a green compact with a single weight of 3.0 kg at a pressure of 180 MPa by isostatic pressing, and the green compact was pre-sintered at a low temperature in a hydrogen atmosphere to increase the strength of the green compact;

[0179] 7. Use high temperature sintering method, and use the method of rapid heating and extended insulation time at the intermediate insulation point: the sintering temperature curve is:

[0180] Heating from room temperature to A1, heating time H1 is 6h, A1 is 1100℃; keeping at A1 for H2 hours, H2 is 2; heating from A1 to A2, heating time H3, H3 is 2h, A2 is 1400℃; keeping at A2 for H4 hours, H4 is 3.5; heating from A2 to A3, heating time H5, H5 is 2h, A3 is 1800℃; keeping at A3 for H6 hours, H6 is 2; heating from A3 to A4, heating time H7, H7 is 2h, A4 is 2100℃; keeping at A4 for H8 hours, H8 is 6; cooling naturally from A4, the result is obtained. Among them, by controlling the time of medium frequency sintering, the closure and shrinkage speed of the billet pores can be controlled, so as to obtain oxide particles with a particle size of <2.0μm and a density of 18.0g / cm 3Sintered billet.

[0181] 8. Use multiple rotary forging and drawing processes to process the 17mm diameter sintered billet into 2.0mm specification wire, and then perform oxidation annealing on the oxidation annealing equipment, where the annealing conditions are: temperature 1400℃, annealing speed 5m / min; after annealing, continue to process into 0.52mm±0.005mm diameter rare earth tungsten alloy black wire;

[0182] Among them, the multi-pass rotary forging and drawing processing adopts conventional drawing process, and the process parameters are multi-pass rotary forging to a wire diameter specification of 3.7mm, then drawing to 2.0mm, and then further processing to 0.52±0.005mm tungsten lanthanum alloy black wire after annealing.

[0183] 9. Use electrolytic cleaning to clean the 0.52mm black wire into 0.50mm±0.005mm tungsten-lanthanum alloy white wire that can be processed into the filament of microwave oven heating devices;

[0184] 10. Wind 0.50mm tungsten-lanthanum alloy white wire into a spring-shaped cathode filament for heating devices, with 10 turns and a pitch of 1.29±0.03mm;

[0185] 11. Assemble the filament, components, ceramics, lead pieces and other parts into a cathode structure through heat treatment at a temperature of 600°C.

[0186] 12. Weld the filament in the cathode structure to the end cap of the assembly.

[0187] 13. Place the cathode structure into the carbonization tank for carbonization, introduce carbon-containing hydrocarbon gas (specifically methane) after exhausting, and apply direct current of a certain current value (current value is 16A) to heat the cathode to complete carbonization of the filament in the hydrocarbon gas.

[0188] 14. White ball assembly: Assemble the cathode structure, anode cylinder, antenna end cap and other components together.

[0189] 15. Exhaust the white ball, evacuate it, and perform high-temperature aging to complete the manufacture of the black ball and activate its launch performance.

[0190] 16. Assemble the black ball, heat sink, magnet, tube shell, etc. to finally obtain the heating device component containing the above-mentioned filament, and put it into a microwave oven for use.

[0191] Example 2

[0192] 1. According to the formula in Table 1, add 5L of deionized water to a certain amount of lanthanum nitrate-yttrium nitrate solution, stir for 10 minutes to fully dissolve, then add 1L of ammonia NH3·H2O solution and stir to neutralize, spray the prepared mixed solution evenly onto the blue tungsten placed in the doping pot and stir; wherein, the volume ratio of lanthanum nitrate-yttrium nitrate solution to ammonia NH3·H2O solution is 5:1.

[0193] 2. Evacuate the doping pot and heat it with water (heating temperature 80°C, vacuum degree -0.025MPa), stirring while heating;

[0194] 3. Under vacuum, the powder is dried by steam heating, the steam pressure is 0.1-0.3MPa, the vacuum degree in the pot is ≤-0.02MPa, and finally tungsten lanthanum yttrium doped powder with uniform doping and low impurity content is obtained;

[0195] 4. In a reduction furnace with four temperature zones at 650°C, 750°C, 850°C and 900°C, the tungsten lanthanum yttrium doped powder is reduced into tungsten lanthanum yttrium powder of appropriate particle size;

[0196] 5. Put the obtained tungsten lanthanum yttrium powder and tungsten carbide into a high-speed powder mixer for solid-solid powder mixing for 2 hours, and sieve to obtain the mixed tungsten lanthanum yttrium alloy powder;

[0197] 6. The powder with a particle size of 1.5 μm was pressed into a green compact with a single weight of 3.0 kg at a pressure of 180 MPa by isostatic pressing, and the green compact was pre-sintered at a low temperature in a hydrogen atmosphere to increase the strength of the green compact;

[0198] 7. Use high temperature sintering method, and use the method of rapid heating and extended insulation time at the intermediate insulation point: the sintering temperature curve is:

[0199] Heat up from room temperature to A1, the heating time H1 is 5h, A1 is 950℃; keep warm at A1 for H2 hours, H2 is 3; heat up from A1 to A2, the heating time is H3, H3 is 1.5h, A2 is 1300℃; keep warm at A2 for H4 hours, H4 is 4.5; heat up from A2 to A3, the heating time is H5, H5 is 1h, A3 is 1700℃; keep warm at A3 for H6 hours, H6 is 3; heat up from A3 to A4, the heating time is H7, H7 is 1h, A4 is 2050℃; keep warm at A4 for H8 hours, H8 is 10; cool naturally from A4, and you're done.

[0200] 8. The 17 mm diameter sintered billet was processed into a 2.0 mm specification wire by multi-pass rotary forging and drawing, and then oxidative annealing was performed on an oxidative annealing device, wherein the annealing conditions were: temperature 1200° C., annealing speed 3 m / min; after annealing, it was further processed into a 0.52 mm ± 0.005 mm diameter tungsten lanthanum yttrium alloy black wire; the other conditions were consistent with Example 1.

[0201] 9. Use electrolytic cleaning to clean the 0.52mm black wire into 0.50mm±0.005mm tungsten-lanthanum-yttrium alloy white wire that can be processed into the filament of microwave oven heating device;

[0202] 10. Wind 0.50mm tungsten-lanthanum-yttrium alloy white wire into a spring-shaped cathode filament for a heating device; the number of turns is 10, and the pitch is 1.29±0.03mm;

[0203] 11. Assemble the filament, components, ceramics, lead pieces and other parts into a cathode structure through heat treatment at a temperature of 600°C.

[0204] 12. Weld the filament in the cathode structure to the end cap of the assembly.

[0205] 13. Place the cathode structure into the carbonization tank for carbonization, introduce carbon-containing hydrocarbon gas (specifically methane) after exhausting, and apply direct current of a certain current value (current value is 16A) to heat the cathode to complete carbonization of the filament in the hydrocarbon gas.

[0206] 14. White ball assembly: Assemble the cathode structure, anode cylinder, antenna end cap and other components together.

[0207] 15. Exhaust the white ball, evacuate it, and perform high-temperature aging to complete the manufacture of the black ball and activate its launch performance.

[0208] 16. Assemble the black ball, heat sink, magnet, tube shell, etc. to finally obtain the heating device component containing the above-mentioned filament, and put it into a microwave oven for use.

[0209] Example 3

[0210] 1. According to the formula in Table 1, add 5L of deionized water to a certain amount of lanthanum nitrate-zirconium nitrate solution, stir for 10 minutes to fully dissolve, then add 1L of ammonia NH3·H2O solution and stir to neutralize, and evenly spray the prepared mixed solution onto the blue tungsten placed in the doping pot and stir; wherein, the ratio of lanthanum nitrate-zirconium nitrate solution to ammonia NH3·H2O solution is 5:1;

[0211] 2. Evacuate the doping pot and heat it with water (heating temperature 80°C, vacuum degree -0.025MPa), stirring while heating;

[0212] 3. Under vacuum, the powder is dried by steam heating, the steam pressure is 0.1~0.3MPa, the vacuum degree in the pot is ≤-0.02MPa, and finally tungsten lanthanum zirconium doped powder with uniform doping and low impurity content is obtained;

[0213] 4. In a reduction furnace with four temperature zones at 650°C, 750°C, 850°C and 900°C, the tungsten lanthanum zirconium doped powder is reduced into tungsten lanthanum zirconium powder of appropriate particle size;

[0214] 5. Put the obtained tungsten lanthanum zirconium powder and tungsten carbide into a high-speed powder mixer for solid-solid powder mixing for 2 hours, and sieve to obtain the mixed tungsten lanthanum zirconium alloy powder;

[0215] 6. The powder with a particle size of 1.5 μm was pressed into a green compact with a single weight of 3.0 kg at a pressure of 180 MPa by isostatic pressing, and the green compact was pre-sintered at a low temperature in a hydrogen atmosphere to increase the strength of the green compact;

[0216] 7. Use high temperature sintering method, and use the method of rapid heating and extended insulation time at the intermediate insulation point: the sintering temperature curve is:

[0217] From room temperature to A1, the heating time is H1 for 8 hours, A1 is 1250℃; keep at A1 for H2 hours, H2 is 1; from A1 to A2, the heating time is H3, H3 is 2.5 hours, A2 is 1500℃;

[0218] Keep warm at A2 for H4 hours, H4 is 2.5; heat up from A2 to A3, the heating time is H5, H5 is 3h, A3 is 1900℃; keep warm at A3 for H6 hours, H6 is 1; heat up from A3 to A4, the heating time is H7, H7 is 3h, A4 is 2250℃; keep warm at A4 for H8 hours, H8 is 5; cool naturally from A4, and you're done.

[0219] 8. The 17mm diameter sintered billet is processed into 2.0mm specification wire by multi-pass rotary forging and drawing, and then oxidized annealing is carried out on an oxidized annealing device, wherein the annealing conditions are: temperature 1500°C, annealing speed 10m / min; after annealing, it is further processed into 0.52mm±0.005mm diameter tungsten lanthanum zirconium alloy black wire;

[0220] 9. The 0.52 mm black wire is cleaned by electrolytic cleaning to become a 0.50 mm ± 0.005 mm tungsten lanthanum zirconium alloy white wire that can be processed into a filament of a microwave oven heating device; other conditions are consistent with Example 1.

[0221] 10. Wind 0.50mm tungsten lanthanum zirconium alloy white wire into a spring-shaped cathode filament for the heating device; the number of turns is 10, and the pitch is 1.29±0.03mm;

[0222] 11. Assemble the filament, components, ceramics, lead pieces and other parts into a cathode structure through heat treatment at a temperature of 600°C.

[0223] 12. Weld the filament in the cathode structure to the end cap of the assembly.

[0224] 13. Place the cathode structure into the carbonization tank for carbonization, introduce carbon-containing hydrocarbon gas (specifically methane) after exhausting, and apply direct current of a certain current value (current value is 16A) to heat the cathode to complete carbonization of the filament in the hydrocarbon gas.

[0225] 14. White ball assembly: Assemble the cathode structure, anode cylinder, antenna end cap and other components together.

[0226] 15. Exhaust the white ball, evacuate it, and perform high-temperature aging to complete the manufacture of the black ball and activate its launch performance.

[0227] 16. Assemble the black ball, heat sink, magnet, tube shell, etc. to finally obtain the heating device component containing the above-mentioned filament, and put it into a microwave oven for use.

[0228] Example 4

[0229] 1. According to the formula in Table 1, add 5L of deionized water to a certain amount of lanthanum nitrate-scandium nitrate solution, stir for 10 minutes to fully dissolve, then add 1L of ammonia NH3·H2O solution and stir to neutralize, spray the prepared mixed solution evenly onto the blue tungsten placed in the doping pot and stir; wherein, the ratio of lanthanum nitrate-scandium nitrate solution to ammonia NH3·H2O solution is 5:1.

[0230] 2. Evacuate the doping pot and heat it with water (heating temperature 80°C, vacuum degree -0.025MPa), stirring while heating;

[0231] 3. Under vacuum, the powder is dried by steam heating, with a steam pressure of 0.1-0.3MPa and a vacuum degree in the pot of ≤-0.02MPa, and finally a tungsten-lanthanum-sc doped powder with uniform doping and low impurity content is obtained;

[0232] 4. In a reduction furnace with four temperature zones at 650°C, 750°C, 850°C and 900°C, the tungsten-lanthanum-scandium doped powder is reduced into tungsten-lanthanum-scandium powder of appropriate particle size;

[0233] 5. Put the obtained tungsten lanthanum scandium powder and tungsten carbide into a high-speed powder mixer for solid-solid powder mixing for 2 hours, and sieve to obtain the mixed tungsten lanthanum scandium alloy powder;

[0234] 6. The powder with a particle size of 1.5 μm was pressed into a green compact with a single weight of 3.0 kg at a pressure of 180 MPa by isostatic pressing, and the green compact was pre-sintered at a low temperature in a hydrogen atmosphere to increase the strength of the green compact;

[0235] 7. Use high temperature sintering to obtain oxide particles with a particle size of <2.0μm and a density of 18.0g / cm 3 The sintered billet; wherein the process and conditions of this step are consistent with those of Example 1;

[0236] 8. Using multiple rotary forging and drawing processes, the 17 mm diameter sintered billet is processed into a 0.52 mm ± 0.005 mm diameter tungsten lanthanum scandium alloy black wire; wherein the process and conditions of this step are consistent with those of Example 1;

[0237] 9. Use electrolytic cleaning to clean the 0.52mm black wire into 0.50mm±0.005mm tungsten lanthanum scandium alloy white wire that can be processed into microwave oven heating device filament;

[0238] 10. Wind 0.50mm tungsten-lanthanum-scandium alloy white wire into a spring-shaped cathode filament for a heating device; the number of turns is 10, and the pitch is 1.29±0.03mm;

[0239] 11. Assemble the filament, components, ceramics, lead pieces and other parts into a cathode structure through heat treatment at a temperature of 600°C.

[0240] 12. Weld the filament in the cathode structure to the end cap of the assembly.

[0241] 13. Place the cathode structure into the carbonization tank for carbonization, introduce carbon-containing hydrocarbon gas (specifically methane) after exhausting, and apply direct current of a certain current value (current value is 16A) to heat the cathode to complete carbonization of the filament in the hydrocarbon gas.

[0242] 14. White ball assembly: Assemble the cathode structure, anode cylinder, antenna end cap and other components together.

[0243] 15. Exhaust the white ball, evacuate it, and perform high-temperature aging to complete the manufacture of the black ball and activate its launch performance.

[0244] 16. Assemble the black ball, heat sink, magnet, tube shell, etc. to finally obtain the heating device component containing the above-mentioned filament, and put it into a microwave oven for use.

[0245] Example 5

[0246] 1. According to the formula in Table 1, add 5L of deionized water to a certain amount of lanthanum nitrate-hafnium nitrate solution, stir for 10 minutes to fully dissolve, then add 1L of ammonia NH3·H2O solution and stir to neutralize, and evenly spray the prepared mixed solution onto the blue tungsten placed in the doping pot and stir; wherein, the ratio of lanthanum nitrate-hafnium nitrate solution to ammonia NH3·H2O solution is 5:1;

[0247] 2. Evacuate the doping pot and heat it with water (heating temperature 80°C, vacuum degree -0.025MPa), stirring while heating;

[0248] 3. Under vacuum, the powder is dried by steam heating, with a steam pressure of 0.1-0.3MPa and a vacuum degree in the pot of ≤-0.02MPa, to finally obtain tungsten, lanthanum and hafnium doped powder with uniform doping and low impurity content;

[0249] 4. In a reduction furnace with four temperature zones at 650°C, 750°C, 850°C and 900°C, the tungsten lanthanum hafnium doped powder is reduced into tungsten lanthanum hafnium powder with a suitable particle size and a content of 0.3% La2O3+0.2% HfO2;

[0250] 5. The obtained tungsten lanthanum hafnium powder and tungsten carbide are put into a high-speed powder mixer for solid-solid powder mixing for 2 hours, and sieved to obtain a mixed tungsten lanthanum hafnium alloy powder with a content of 0.3% La2O3+0.2% HfO2+0.5% WC;

[0251] 6. The powder with a particle size of 1.5 μm was pressed into a green compact with a single weight of 3.0 kg at a pressure of 180 MPa by isostatic pressing, and the green compact was pre-sintered at a low temperature in a hydrogen atmosphere to increase the strength of the green compact;

[0252] 7. Use high temperature sintering to obtain oxide particles with a particle size of <2.0μm and a density of 18.0g / cm 3 The sintered billet; wherein the process and conditions of this step are consistent with those of Example 1;

[0253] 8. The 17 mm diameter sintered billet is processed into a 0.52 mm ± 0.005 mm diameter tungsten lanthanum hafnium alloy black wire by multiple rotary forging and drawing processes; wherein the process and conditions of this step are consistent with those of Example 1;

[0254] 9. Use electrolytic cleaning to clean the 0.52mm black wire into 0.50mm±0.005mm tungsten lanthanum hafnium alloy white wire that can be processed into microwave oven heating device filament;

[0255] 10. Wind 0.50mm tungsten-lanthanum-hafnium alloy white wire into a spring-shaped cathode filament for a heating device; the number of turns is 10, and the pitch is 1.29±0.03mm;

[0256] 11. Assemble the filament, components, ceramics, lead pieces and other parts into a cathode structure through heat treatment at a temperature of 600°C.

[0257] 12. Weld the filament in the cathode structure to the end cap of the assembly.

[0258] 13. Place the cathode structure into the carbonization tank for carbonization, introduce carbon-containing hydrocarbon gas (specifically methane) after exhausting, and apply direct current of a certain current value (current value is 16A) to heat the cathode to complete carbonization of the filament in the hydrocarbon gas.

[0259] 14. White ball assembly: Assemble the cathode structure, anode cylinder, antenna end cap and other components together.

[0260] 15. Exhaust the white ball, evacuate it, and perform high-temperature aging to complete the manufacture of the black ball and activate its launch performance.

[0261] 16. Assemble the black ball, heat sink, magnet, tube shell, etc. to finally obtain the heating device component containing the above-mentioned filament, and put it into a microwave oven for use.

[0262] Example 6

[0263] 1. According to the formula in Table 1, add 5L of deionized water to a certain amount of lanthanum nitrate-hafnium nitrate solution, stir for 10 minutes to fully dissolve, then add 1L of ammonia NH3·H2O solution and stir to neutralize, and evenly spray the prepared mixed solution onto the blue tungsten placed in the doping pot and stir; wherein, the ratio of lanthanum nitrate-hafnium nitrate solution to ammonia NH3·H2O solution is 5:1;

[0264] 2. Evacuate the doping pot and heat it with water (heating temperature 80°C, vacuum degree -0.025MPa), stirring while heating;

[0265] 3. Under vacuum, the powder is dried by steam heating, with a steam pressure of 0.1-0.3MPa and a vacuum degree in the pot of ≤-0.02MPa, to finally obtain tungsten, lanthanum and hafnium doped powder with uniform doping and low impurity content;

[0266] 4. In a reduction furnace with four temperature zones at 650°C, 750°C, 850°C and 900°C, the tungsten lanthanum hafnium doped powder is reduced into tungsten lanthanum hafnium powder with a suitable particle size and a content of 2.0% La2O3+1.0% HfO2;

[0267] 5. The obtained tungsten lanthanum hafnium powder and tungsten carbide are put into a high-speed powder mixer for solid-solid powder mixing for 2 hours, and sieved to obtain a mixed tungsten lanthanum hafnium alloy powder with a content of 2.0% La2O3+1.0% HfO2+2.0% WC;

[0268] 6. The powder with a particle size of 1.5 μm was pressed into a green compact with a single weight of 3.0 kg at a pressure of 180 MPa by isostatic pressing, and the green compact was pre-sintered at a low temperature in a hydrogen atmosphere to increase the strength of the green compact;

[0269] 7. Use high temperature sintering to obtain oxide particles with a particle size of <2.0μm and a density of 18.0g / cm 3 The sintered billet; wherein the process and conditions of this step are consistent with those of Example 1;

[0270] 8. The 17 mm diameter sintered billet is processed into a 0.52 mm ± 0.005 mm diameter tungsten lanthanum hafnium alloy black wire by multiple rotary forging and drawing processes; wherein the process and conditions of this step are consistent with those of Example 1;

[0271] 9. Use electrolytic cleaning to clean the 0.52mm black wire into 0.50mm±0.005mm tungsten lanthanum hafnium alloy white wire that can be processed into microwave oven heating device filament;

[0272] 10. Wind 0.50mm tungsten-lanthanum-hafnium alloy white wire into a spring-shaped cathode filament for a heating device; the number of turns is 10, and the pitch is 1.29±0.03mm;

[0273] 11. Assemble the filament, components, ceramics, lead pieces and other parts into a cathode structure through heat treatment at a temperature of 600°C.

[0274] 12. Weld the filament in the cathode structure to the end cap of the assembly.

[0275] 13. Place the cathode structure into the carbonization tank for carbonization, introduce carbon-containing hydrocarbon gas (specifically methane gas) after exhausting, and apply direct current of a certain current value (current value is 16A) to heat the cathode to complete carbonization of the filament in the hydrocarbon gas.

[0276] 14. White ball assembly: Assemble the cathode structure, anode cylinder, antenna end cap and other components together.

[0277] 15. Exhaust the white ball, evacuate it, and perform high-temperature aging to complete the manufacture of the black ball and activate its launch performance.

[0278] 16. Assemble the black ball, heat sink, magnet, tube shell, etc. to finally obtain the heating device component containing the above-mentioned filament, and put it into a microwave oven for use.

[0279] Example 7

[0280] 1. According to the formula in Table 1, add a certain amount of lanthanum nitrate to 5L deionized water, stir for 10 minutes to fully dissolve, then add 1L ammonia NH3·H2O solution and stir to neutralize, spray the prepared mixed solution evenly onto the blue tungsten placed in the doping pot and stir; wherein, the volume ratio of lanthanum nitrate solution to ammonia NH3·H2O solution is 5:1;

[0281] 2. Evacuate the doping pot and heat it with water (heating temperature 80°C, vacuum degree -0.025MPa), stirring while heating;

[0282] 3. Under vacuum, the powder is dried by steam heating, the steam pressure is 0.1~0.3MPa, the vacuum degree in the pot is ≤-0.02MPa, and finally tungsten-lanthanum doped powder with uniform doping and low impurity content is obtained;

[0283] 4. Reduce the tungsten-lanthanum doped powder into tungsten-lanthanum powder of suitable particle size in a reduction furnace with four temperature zones at 650°C, 750°C, 850°C and 900°C;

[0284] 5. According to the formula in Table 1, add 5L of deionized water into the doping pot and heat it to 80°C, then add a certain amount of ammonium rhenate, stir for 10 minutes to fully dissolve, add a certain amount of tungsten lanthanum powder into the ammonium rhenate solution and stir for 30 minutes, then dry the powder by steam heating under vacuum, the steam pressure is 0.1~0.3MPa, the vacuum degree in the pot is ≤-0.02MPa, and finally obtain rhenium-doped tungsten lanthanum powder with uniform doping and low impurity content;

[0285] 6. Reduce the rhenium-doped tungsten-lanthanum powder into tungsten-lanthanum-rhenium alloy powder with a particle size of 1.5 μm in a reduction furnace with four temperature zones at 650°C, 750°C, 850°C and 900°C;

[0286] 7. The obtained tungsten-lanthanum-rhenium alloy powder and tungsten carbide are placed in a high-speed powder mixer for solid-solid powder mixing for 2 hours, and the mixed tungsten-lanthanum-rhenium alloy powder is obtained by sieving;

[0287] 8. The powder with a particle size of 1.5 μm was pressed into a green compact with a single weight of 3.0 kg at a pressure of 180 MPa by isostatic pressing, and the green compact was pre-sintered at a low temperature in a hydrogen atmosphere to increase the strength of the green compact;

[0288] 9. Use high temperature sintering to obtain oxide particles with a particle size of <2.0μm and a density of 18.0g / cm 3 The sintered billet; wherein the process and conditions of this step are consistent with those of Example 1;

[0289] 10. The 17 mm diameter sintered billet is processed into a 0.52 mm ± 0.005 mm diameter tungsten lanthanum rhenium alloy black wire by multiple rotary forging and drawing processes; wherein the process and conditions of this step are consistent with those of Example 1;

[0290] 11. Use electrolytic cleaning to clean the 0.52mm black wire into 0.50mm±0.005mm tungsten lanthanum rhenium alloy white wire that can be processed into microwave oven heating device filament;

[0291] 12. Wind 0.50mm tungsten-lanthanum-rhenium alloy white wire into a spring-shaped cathode filament for heating devices, with 10 turns and a pitch of 1.29±0.03mm;

[0292] 13. Assemble the filament, components, ceramics, lead pieces and other parts into a cathode structure through heat treatment at a temperature of 600°C.

[0293] 14. Weld the filament in the cathode structure to the end cap of the assembly.

[0294] 15. Place the cathode structure into the carbonization tank for carbonization, exhaust the gas, introduce carbon-containing hydrocarbon gas (specifically methane), and heat the cathode with a direct current of a certain current value (current value is 16A) to complete the carbonization of the filament in the hydrocarbon gas.

[0295] 16. White ball assembly: Assemble the cathode structure, anode cylinder, antenna end cap and other components together.

[0296] 17. The white ball is evacuated and aged at high temperature to complete the manufacture of the black ball and activate its launch performance.

[0297] 18. Assemble the black ball, heat sink, magnet, tube shell, etc. to finally obtain the heating device component containing the above-mentioned filament, and put it into a microwave oven for use.

[0298] Comparative Example 1:

[0299] 1. According to the formula in Table 1, add 5L of deionized water to a certain amount of thorium nitrate solution, stir for 10 minutes to fully dissolve, then add 1L of ammonia NH3·H2O solution and stir to neutralize, and evenly spray the prepared mixed solution onto the blue tungsten placed in the doping pot and stir; wherein, the ratio of thorium nitrate solution to ammonia NH3·H2O solution is 5:1;

[0300] 2. Evacuate the doping pot and heat it with water (heating temperature 80°C, vacuum degree -0.025MPa), stirring while heating;

[0301] 3. Under vacuum, the powder is dried by steam heating, the steam pressure is 0.1~0.3MPa, the vacuum degree in the pot is ≤-0.02MPa, and finally thorium tungsten doped powder with uniform doping and low impurity content is obtained;

[0302] 4. The thoriated tungsten doped powder is reduced into thoriated tungsten powder with a particle size of 1.5 μm in a reduction furnace with four temperature zones at 650°C, 750°C, 850°C and 900°C;

[0303] 5. The obtained thoriated tungsten powder is put into a V-type powder mixer for mixing for 2 hours, and then sieved to obtain the mixed thoriated tungsten powder;

[0304] 6. Use isostatic pressing to press 1.5μm thoriated tungsten powder into a green compact weighing 3.0kg at a pressure of 180MPa, and pre-sinter the green compact at low temperature in a hydrogen atmosphere to increase the green compact strength;

[0305] 7.Use high temperature sintering to obtain thorium oxide particles with a particle size of <2.0μm and a density of 18.0g / cm 3 The sintered billet; wherein the process and conditions of this step are consistent with those of Example 1;

[0306] 8. The 17 mm diameter sintered billet is processed into a 0.52 mm ± 0.005 mm diameter thoriated tungsten alloy black wire by multiple rotary forging and drawing processes; wherein the process and conditions of this step are consistent with those of Example 1;

[0307] 9. Use electrolytic cleaning to clean the 0.52mm black wire into 0.50mm±0.005mm thoriated tungsten alloy white wire that can be processed into the filament of microwave oven heating device;

[0308] 10. Wind 0.50mm thoriated tungsten white wire into a spring-shaped cathode filament for a heating device; the number of turns is 10, and the pitch is 1.29±0.03mm;

[0309] 11. Assemble the filament, components, ceramics, lead pieces and other parts into a cathode structure through heat treatment at a temperature of 600°C.

[0310] 12. Weld the filament in the cathode structure to the end cap of the assembly.

[0311] 13. Place the cathode structure into the carbonization tank for carbonization, introduce carbon-containing hydrocarbon gas (methane gas) after exhausting, and apply direct current of a certain current value (current value is 16A) to heat the cathode to complete carbonization of the filament in the hydrocarbon gas.

[0312] 14. White ball assembly: Assemble the cathode structure, anode cylinder, antenna end cap and other components together.

[0313] 15. Exhaust the white ball, evacuate it, and perform high-temperature aging to complete the manufacture of the black ball and activate its launch performance.

[0314] 16. Assemble the black ball, heat sink, magnet, tube shell, etc. to finally obtain the heating device component containing the above-mentioned filament, and put it into a microwave oven for use.

[0315] Comparative Example 2:

[0316] 1. According to the formula in Table 1, add 5L of deionized water to a certain amount of lanthanum nitrate-yttrium nitrate solution, stir for 10 minutes to fully dissolve, then add 1L of ammonia NH3·H2O solution and stir to neutralize, spray the prepared mixed solution evenly onto the blue tungsten placed in the doping pot and stir; wherein, the ratio of lanthanum nitrate-yttrium nitrate solution to ammonia NH3·H2O solution is 5:1.

[0317] 2. Evacuate the doping pot and heat it with water (heating temperature 80°C, vacuum degree -0.025MPa), stirring while heating;

[0318] 3. Under vacuum, the powder is dried by steam heating, the steam pressure is 0.1-0.3MPa, the vacuum degree in the pot is ≤-0.02MPa, and finally tungsten lanthanum yttrium doped powder with uniform doping and low impurity content is obtained;

[0319] 4. In a reduction furnace with four temperature zones at 650°C, 750°C, 850°C and 900°C, the tungsten lanthanum yttrium doped powder is reduced into tungsten lanthanum yttrium powder with a particle size of 1.5 μm;

[0320] 5. The obtained tungsten lanthanum yttrium powder is put into a V-type powder mixer for mixing for 2 hours, and then sieved to obtain a mixed tungsten lanthanum yttrium alloy powder;

[0321] 6. Use isostatic pressing to press the 1.5 μm tungsten-lanthanum-yttrium alloy powder into a green compact weighing 3.0 kg at a pressure of 180 MPa, and pre-sinter the green compact at a low temperature in a hydrogen atmosphere to increase the green compact strength;

[0322] 7. Use high temperature sintering to obtain oxide particles with a particle size of <2.0μm and a density of 18.0g / cm 3 The sintered billet; wherein the process and conditions of this step are consistent with those of Example 1;

[0323] 8. Using multiple rotary forging and drawing processes, the 17 mm diameter sintered billet is processed into a 0.52 mm ± 0.005 mm diameter tungsten lanthanum yttrium alloy black wire; wherein the process and conditions of this step are consistent with those of Example 1;

[0324] 9. Use electrolytic cleaning to clean the 0.52mm black wire into 0.50mm±0.005mm tungsten-lanthanum-yttrium alloy white wire that can be processed into the filament of microwave oven heating device;

[0325] 10. Wind 0.50mm tungsten-lanthanum-yttrium alloy white wire into a spring-shaped cathode filament for a heating device; the number of turns is 10, and the pitch is 1.29±0.03mm;

[0326] 11. Assemble the filament, components, ceramics, lead pieces and other parts into a cathode structure through heat treatment at a temperature of 600°C.

[0327] 12. Weld the filament in the cathode structure to the end cap of the assembly.

[0328] 13. Place the cathode structure into the carbonization tank for carbonization, introduce carbon-containing hydrocarbon gas (specifically methane) after exhausting, and apply direct current of a certain current value (current value is 16A) to heat the cathode to complete carbonization of the filament in the hydrocarbon gas.

[0329] 14. White ball assembly: Assemble the cathode structure, anode cylinder, antenna end cap and other components together.

[0330] 15. Exhaust the white ball, evacuate it, and perform high-temperature aging to complete the manufacture of the black ball and activate its launch performance.

[0331] 16. Assemble the black ball, heat sink, magnet, tube shell, etc. to finally obtain the heating device component containing the above-mentioned filament, and put it into a microwave oven for use.

[0332] Comparative Example 3:

[0333] 1. According to the formula in Table 1, add 5L of deionized water to a certain amount of lanthanum nitrate-scandium nitrate solution, stir for 10 minutes to fully dissolve, then add 1L of ammonia NH3·H2O solution and stir to neutralize, spray the prepared mixed solution evenly onto the blue tungsten placed in the doping pot and stir; wherein, the ratio of lanthanum nitrate-scandium nitrate solution to ammonia NH3·H2O solution is 5:1.

[0334] 2. Evacuate the doping pot and heat it with water (heating temperature 80°C, vacuum degree -0.025MPa), stirring while heating;

[0335] 3. Under vacuum, the powder is dried by steam heating, the steam pressure is 0.1-0.3MPa, and the vacuum degree in the pot is ≤-0.02MPa, and finally tungsten lanthanum scandium doped powder with uniform doping and low impurity content is obtained;

[0336] 4. In a reduction furnace with four temperature zones at 650°C, 750°C, 850°C and 900°C, the tungsten-lanthanum-scandium doped powder is reduced into tungsten-lanthanum-scandium powder with a particle size of 1.5 μm;

[0337] 5. The obtained tungsten lanthanum scandium powder is put into a V-type powder mixer for mixing for 2 hours, and then sieved to obtain a mixed tungsten lanthanum scandium alloy powder;

[0338] 6. The powder with a particle size of 1.5 μm was pressed into a green compact with a single weight of 3.0 kg at a pressure of 180 MPa by isostatic pressing, and the green compact was pre-sintered at a low temperature in a hydrogen atmosphere to increase the strength of the green compact;

[0339] 7. Use high temperature sintering to obtain oxide particles with a particle size of <2.0μm and a density of 18.0g / cm 3 The sintered billet; wherein the process and conditions of this step are consistent with those of Example 1;

[0340] 8. Using multiple rotary forging and drawing processes, the 17 mm diameter sintered billet is processed into a 0.52 mm ± 0.005 mm diameter tungsten lanthanum scandium alloy black wire; wherein the process and conditions of this step are consistent with those of Example 1;

[0341] 9. Use electrolytic cleaning to clean the 0.52mm black wire into 0.50mm±0.005mm tungsten lanthanum scandium alloy white wire that can be processed into microwave oven heating device filament;

[0342] 10. Wind 0.50mm tungsten-lanthanum-scandium alloy white wire into a spring-shaped cathode filament for a heating device; the number of turns is 10, and the pitch is 1.29±0.03mm;

[0343] 11. Assemble the filament, components, ceramics, lead pieces and other parts into a cathode structure through heat treatment at a temperature of 600 degrees Celsius.

[0344] 12. Weld the filament in the cathode structure to the end cap of the assembly.

[0345] 13. Place the cathode structure into a carbonization tank for carbonization, introduce carbon-containing hydrocarbon gas (preferably methane gas) after exhausting, and apply direct current of a certain current value (preferably 16A) to the cathode for heating, so that the filament is carbonized in the hydrocarbon gas.

[0346] 14. White ball assembly: Assemble the cathode structure, anode cylinder, antenna end cap and other components together.

[0347] 15. Exhaust the white ball, evacuate it, and perform high-temperature aging to complete the manufacture of the black ball and activate its launch performance.

[0348] 16. Assemble the black ball, heat sink, magnet, tube shell, etc. to finally obtain the heating device component (i.e., heating device) containing the above-mentioned filament, and put it into a microwave oven for use.

[0349] Comparative Example 4:

[0350] The cathode filament of Example 1 is used, and the carbonization current in the carbonization process of Example 1 is increased by 2A, so that the grains of the carbonized structure are increased, and the grain width is increased from 3-10 μm in Example 1 to 10-30 μm.

[0351] It should be noted that one of the means to control the grain size is to control the carbonization current. By adjusting the carbonization current, the grain size can be controlled within the desired range. The design point of the present application to achieve the desired effect is to control the grain size within the specified range of the present application.

[0352] Comparative Example 5

[0353] 1. According to the formula in Table 1, add a certain amount of lanthanum nitrate to 5L deionized water, stir for 10 minutes to fully dissolve, then add 1L ammonia NH3·H2O solution and stir to neutralize, spray the prepared mixed solution evenly onto the blue tungsten placed in the doping pot and stir; wherein, the volume ratio of lanthanum nitrate solution to ammonia NH3·H2O solution is 5:1;

[0354] 2. Evacuate the doping pot and heat it with water (heating temperature 80°C, vacuum degree -0.025MPa), stirring while heating;

[0355] 3. Under vacuum, the powder is dried by steam heating, the steam pressure is 0.1~0.3MPa, the vacuum degree in the pot is ≤-0.02MPa, and finally tungsten-lanthanum doped powder with uniform doping and low impurity content is obtained;

[0356] 4. Reduce the tungsten-lanthanum doped powder into tungsten-lanthanum powder of suitable particle size in a reduction furnace with four temperature zones at 650°C, 750°C, 850°C and 900°C;

[0357] 5. According to the formula in Table 1, add 5L of deionized water into the doping pot and heat it to 80°C, then add a certain amount of ammonium rhenate, stir for 10 minutes to fully dissolve, add a certain amount of tungsten lanthanum powder into the ammonium rhenate solution and stir for 30 minutes, then dry the powder by steam heating under vacuum, the steam pressure is 0.1~0.3MPa, the vacuum degree in the pot is ≤-0.02MPa, and finally obtain rhenium-doped tungsten lanthanum powder with uniform doping and low impurity content;

[0358] 6. Reduce the rhenium-doped tungsten-lanthanum powder into tungsten-lanthanum-rhenium alloy powder with a particle size of 1.5 μm in a reduction furnace with four temperature zones at 650°C, 750°C, 850°C and 900°C;

[0359] 7. The obtained tungsten-lanthanum-rhenium alloy powder and tungsten carbide are placed in a high-speed powder mixer for solid-solid powder mixing for 2 hours, and the mixed tungsten-lanthanum-rhenium alloy powder is obtained by sieving;

[0360] 8. The powder with a particle size of 1.5 μm was pressed into a green compact with a single weight of 3.0 kg at a pressure of 180 MPa by isostatic pressing, and the green compact was pre-sintered at a low temperature in a hydrogen atmosphere to increase the strength of the green compact;

[0361] 9. Use high temperature sintering to obtain oxide particles with a particle size of <2.0μm and a density of 18.0g / cm 3 The sintered billet; wherein the process and conditions of this step are consistent with those of Example 1;

[0362] 10. The 17 mm diameter sintered billet is processed into a 0.52 mm ± 0.005 mm diameter tungsten lanthanum rhenium alloy black wire by multiple rotary forging and drawing processes; wherein the process and conditions of this step are consistent with those of Example 1;

[0363] 11. Use electrolytic cleaning to clean the 0.52mm black wire into 0.50mm±0.005mm tungsten lanthanum rhenium alloy white wire that can be processed into microwave oven heating device filament;

[0364] 12. Wind 0.50mm tungsten-lanthanum-rhenium alloy white wire into a spring-shaped cathode filament for heating devices, with 10 turns and a pitch of 1.29±0.03mm;

[0365] 13. Assemble the filament, components, ceramics, lead pieces and other parts into a cathode structure through heat treatment at a temperature of 600°C.

[0366] 14. Weld the filament in the cathode structure to the end cap of the assembly.

[0367] 15. Place the cathode structure into the carbonization tank for carbonization, exhaust the gas, introduce carbon-containing hydrocarbon gas (specifically methane), and heat the cathode with a direct current of a certain current value (current value is 16A) to complete the carbonization of the filament in the hydrocarbon gas.

[0368] 16. White ball assembly: Assemble the cathode structure, anode cylinder, antenna end cap and other components together.

[0369] 17. The white ball is evacuated and aged at high temperature to complete the manufacture of the black ball and activate its launch performance.

[0370] 18. Assemble the black ball, heat sink, magnet, tube shell, etc. to finally obtain the heating device component containing the above-mentioned filament, and put it into a microwave oven for use.

[0371] The tungsten alloy wires, tungsten alloy filaments and devices (microwave ovens) containing the filament components prepared in the above embodiments and comparative examples were tested for relevant performance indicators under the same test conditions. The test results are shown in the following table:

[0372] Table 2

[0373]

[0374]

[0375]

[0376] Note: The yield rate statistics refer to the yield rate from billet to finished filament.

[0377] Table 3

[0378]

[0379] In Table 2-3, the test standard for the recrystallization temperature range item is GB T 23272-2009 Tungsten wire for lighting and electronic equipment; FC is the size of the fusing current, and the conversion method for FC% and Celsius is as follows: Fig.21The high temperature performance test method in Article 4.3.2.2 of the GB / T23272-2009 national standard for tungsten filaments for lighting and electronic equipment shows a reference relationship between FC% and temperature, which can be used for conversion; the electron work function is measured according to the Richardson linear method; the working life of the tungsten alloy filament is tested according to Article 6.5.2 of the GB / T 23152-2008 national standard for heating devices for household microwave ovens, wherein the standard requires continuous operation of heating devices for microwave ovens to be >500h; wherein, the preparation process of steps 10-14 in the embodiment and the test nodes for each test item are as follows: Fig. 20 shown.

[0380] 1. Comparison of Example 1 and Comparative Example 1, where Comparative Example 1 is a thoriated tungsten filament:

[0381] The metallographic conditions of Example 1 and Comparative Example 1 at different fusing currents are as follows Figure 5-11 As shown: it can be clearly seen that the recrystallization temperature of Example 1 is 50% FC (about 2120°C), and the recrystallization temperature of Comparative Example 1 is 46% FC (about 2020°C). It can be seen that the initial recrystallization temperature of the filament material of the present application is higher than that of the original thoriated tungsten wire material;

[0382] The grain size of the filament after carbonization in Example 1 and Comparative Example 1 is as follows: Figure 12-13 As shown: Fig.13 In Example 1, the filament structure after carbonization is still a fine-grained structure. Fig.12 The grains of the filament structure after carburization in Comparative Example 1 are obviously larger. From the data, the number of grains of the tungsten substrate 100 after carburization in Example 1 is 4000 / mm 2 , Comparative Example 1 is 100 pieces / mm 2 The grain width of the carbonized layer 200 of Example 1 is 6.83 μm, and that of Comparative Example 1 is 9.81 μm.

[0383] The distribution of the channels 210 of the filaments after carbonization in Example 1 and Comparative Example 1 is as follows: Figure 14-16 As shown, Fig.14 In the carbonized layer 200 of the cross section of the filament after carbonization in the embodiment 1 shown, there are many first channels 211 quasi-vertical to the edge of the filament, and the second channels 212 intersect with the first channels to form a quasi-ring distribution, and the carbonized layer 200 forms a layer block. Fig.15 In the carbonized layer 200 of the longitudinal section of the filament after carbonization in the embodiment 1 shown, there are many first channels 211 which are perpendicular to the edge of the filament; Fig.16In the carbonized layer 200 of the cross-section of the filament after carbonization in Comparative Example 1, the number of first channels 211 perpendicular to the edge of the filament is significantly reduced, and there are very few parallel second channels 212. The reason for this is that the grain width of the carbonized layer in Comparative Example 1 is relatively large, and the number of its channels 210 is related to the size of the grains, and the grain size affects the formation of the channels 210.

[0384] In Example 1 of the present application, the layered structure in the carbonized layer 200 separated by the second channel 212 is where the oxide of M is distributed. The first channel 211 is vertically distributed to the edge of the filament, connecting the interior of the substrate 100, the second channel 212 and the edge of the filament. The second channel 212 is combined with the first channel 211, which is beneficial to the outward migration of rare earth atoms and timely replenishment of rare earth elements evaporated from the surface, thereby improving the stability of material emission.

[0385] 2. Comparing Example 1 with Comparative Example 4, the difference between Comparative Example 4 and Example 1 is that the grain size of the carburized layer is significantly larger:

[0386] Figure 17-18 The channels 210 distributed in the carbonized layer 200 of the cross section and longitudinal section of the carbonized filament in Comparative Example 4 are obviously parallel to the outer edge 220 of the filament, and cannot form a layer block structure. And the data in Table 2-3 show that the emission performance of Example 1 is stable after working for 30 minutes, while the microwave disappearance phenomenon occurs in Comparative Example 4 after working for less than 10 minutes; the emission effect is unstable.

[0387] The analysis of its mechanism is:

[0388] Although in Comparative Example 4, a structure similar to the channel 210 also appears inside the carbonized layer 200, this channel 210 is parallel to the edge of the filament, and the cross-section of the carbonized layer 200 forms a layered structure. The reason for this is that the grain size in the carbonized layer 200 is relatively large, at 23.12 μm, and the grain size affects the formation of the channel 210. It is difficult to form a large number of vertically distributed channels 210 in the carbonized layer 200. The layered structure of the carbonized layer 200 separates the interior of the substrate 100 from the edge of the filament. When rare earth atoms migrate from the inside to the outside, when they encounter the channel 210 parallel to the edge of the filament, their migration is hindered and they cannot diffuse further outward or the diffusion becomes more difficult, so the emission performance is reduced.

[0389] In contrast, in Example 1 of the present application, the grain size in the carbonized layer 200 is small, only 6.83 μm, thereby forming more second channels 212 and more first channels 211 that are cross-distributed, and the carbonized layer 200 forms a layer block. The layered structure in the carbonized layer 200 separated by the second channel 212 is where the oxide of M is distributed. The first channel 211 is vertically distributed to the edge of the filament, connecting the inside of the substrate 100, the second channel 212 and the edge of the filament. The more the number of the above-mentioned channels 210, the more conducive it is to the migration of rare earth atoms. Example 1 combines the second channel 212 with the first channel 211, which is conducive to the outward migration of rare earth atoms and timely replenishment of rare earth elements evaporated from the surface, thereby improving the stability of material emission.

[0390] 3. Comparison of Example 2 and Comparative Example 2, Example 4 and Comparative Example 3:

[0391] 3.1 The difference between Example 2 and Comparative Example 2 is that: No carbide raw material is added to Comparative Example 2, and there is no carbon in its components;

[0392] By comparing the two results, it can be seen that compared with Example 2, the recrystallization temperature of Example 2 is lower, the grain width of the carbide layer is larger, and the carbide layer 200 has a block structure, which is reflected in the performance: its emission performance stability deteriorates, the electron emission performance deteriorates, and the working life is shortened.

[0393] 3.2 The difference between Example 4 and Comparative Example 3 is that: Comparative Example 3 does not add carbide raw materials, and there is no carbon in its components; by comparing the results of the two, it can be seen that: compared with Example 4, the recrystallization temperature of Comparative Example 3 is lower, the grain width of the carbide layer is larger, and the carbide layer 200 has a block structure, which is reflected in the performance: its emission performance stability deteriorates, the electron emission performance deteriorates, and the working life is shortened.

[0394] The analysis of its mechanism is:

[0395] In the embodiments of the present application, by adding one or more oxides and carbides of M or carbon, the oxides and carbides of M in the tungsten matrix will react at high temperature, and the generated M metal atoms are much smaller than the particles of the oxide of M. The migration and diffusion speed of the M metal atoms in the tungsten matrix will be accelerated. Therefore, compared with the thoriated tungsten filament, it can achieve the same or even higher electron emission capability at a lower operating voltage (excitation temperature). However, since no carbon raw material is added to comparative examples 2-3, the above effect cannot be achieved, and its electron emission performance is deteriorated.

[0396] 4. Comparative Example 7 and Comparative Example 5:

[0397] The difference between Example 7 and Comparative Example 5 is that the Re content of Comparative Example 5 exceeds the range specified in this application;

[0398] Comparing the two results, it can be seen that the working temperature of comparative example 5 becomes higher and the working life becomes shorter. The inventor analyzed that rhenium has the functions of purifying grain boundaries and strengthening the solid solution of rhenium and tungsten. However, the rhenium content added exceeds the specified range of this application. The rhenium content is too high, the strengthening effect is too large, and the work hardening is too large, which makes the wire more prone to cracks. It can be clearly seen in the wire flaw detection data that the number of crack points detected in Example 7 is 0.8-1.5 per 100 meters, while that in comparative example 5 is 6-10 per 100 meters.

[0399] In summary, it can be clearly concluded from the test results of the embodiments and comparative examples that:

[0400] 1. The carbonized layer 200 of the cross-sectional structure, longitudinal section structure and longitudinal planing section structure were observed:

[0401] Compared with the thoriated tungsten filament, the grain size of the carbide layer 200 of the thoriated tungsten lanthanum filament in the present application is smaller than that of the thoriated tungsten filament, and the grain width is slightly narrower than that of the thoriated tungsten, so that the number of channels 210 in the carbide layer 200 of the present application is more, and the organization of the carbide layer 200 at different positions in the filament provided in the present application has an organization similar to the cross shape of the first channel 211 and the second channel 212, forming a layer block structure. The first channel 211 is vertically distributed with the edge of the filament, connecting the second channel 212, the inside of the substrate 100 and the edge of the filament, which is conducive to the outward migration of rare earth atoms and timely replenishment of the rare earth element evaporated from the surface, and improving the stability of the material emission. It can be clearly seen from the emission performance stabilization time data in the test results that there are differences in the emission performance of the filaments. Among them, the emission performance of the filament of the present application is stable, which is equivalent to that of the traditional thoriated tungsten filament.

[0402] It can be seen that the tungsten carbide alloy material of the present application replenishes the rare earth element evaporated from the surface through the stable outward migration of rare earth, thereby improving the stability of the material's emission. Without adding thorium elements, it can also achieve the stable emission capability of traditional thorium tungsten filaments, solve the problem of poor stable emission capability of existing thorium-free tungsten filaments, and does not have the radioactive pollution problem of traditional thorium tungsten filaments.

[0403] 2. There is a carbonization process in the preparation of the filament, and the carbonization temperature is 2000-2200℃. The original thoriated tungsten filament is carbonized at this temperature, and the grain structure will show recrystallization. The grains are coarse, which makes the filament very easy to break after carbonization. If the vibration in the production process is slightly larger, the wire will break (the wire breakage rate is about 20,000-30,000 ppm).

[0404] The recrystallization temperatures measured in Examples 1-7 are between 48% FC (about 2070°C) and 52% FC (about 2180°C), and the recrystallization temperature of Comparative Example 1 is 46% FC (about 2020°C). The initial recrystallization temperature of the filament material produced by the present application is higher than that of the original thoriated tungsten filament, and the filament structure after carbonization is still a fine-grained structure (the grain size of the embodiments of the present application is significantly smaller than that of the comparative example), and the filament with a fine-grained structure is not easy to break;

[0405] 3. It can be clearly seen from the test results that the processing performance of the filament material of the present application is better than that of the original thoriated tungsten, the number of flaw detection cracks is less (when the filament wire diameter can reach 500μm, the number of flaw detection cracks of the filament is less than 2 / per 100 meters), the processing yield is high, the wound filament is not easy to break, the production efficiency is improved, and the wire material has fewer cracks, and the proportion of broken wires during carbonization of the manufactured filament is also less.

[0406] 4. It can be clearly seen from the electron emission performance parameters in the test results that the DC emission capacity of the heating device made of the filament of the present application is nearly twice that of the thoriated tungsten filament (Comparative Example 1), so that the heating device made of the filament provided by the present application can excite electrons at a lower voltage (Note: According to the use of heating devices in this field, the starting voltage of the thoriated tungsten heating device must be at least 2.0V. In order to ensure the starting voltage, the working voltage is set at 3.3V, while the starting voltage of Example 1 is 1.4V, and the working voltage can be in the range of 1.6 to 1.8V).

[0407] The operating temperature of the heating device of the present application can be reduced from 1500-1600°C to 1100-1500°C, such as 1200-1300°C, while the operating temperature of the traditional thorium tungsten filament is 1600-1900°C. Therefore, the energy consumption and life of the heating device provided by the present application will be improved.

[0408] In summary, the embodiments of the present application improve the emission stability of the material by controlling the grain size of the carbonized layer 200 and coordinating with the M element component contained in the carbonized layer 200, and replenishing the rare earth element evaporated from the surface layer through the stable outward migration of the rare earth. Without adding the thorium element, the stable emission capability of the traditional thorium tungsten filament can be achieved, solving the problem of the poor stable emission capability of the existing thorium-free tungsten filament, and does not have the radioactive pollution problem of the traditional thorium tungsten filament, which is more environmentally friendly.

[0409] The embodiment of the present application can significantly increase the initial recrystallization temperature of the material by doping the tungsten matrix powder with oxides and carbides of M, and can still obtain extremely fine grains at the same carburization temperature as that of thoriated tungsten. It can improve the processing performance of the material, reduce the wire breakage rate during the production and use of the material, and reduce the electronic work function of the material. It can not only reduce the wire breakage rate and improve the yield rate to reduce production and transportation costs, but also effectively increase the service life of the filament, so that its service life reaches and far exceeds the service life of the existing thoriated tungsten filament.

[0410] In summary, the above technical solution provided by the present application includes at least the following working principles or mechanisms and beneficial effects:

[0411] (1) The grain width of the carbide layer 200 of the filament of the present application is controlled within a certain small size range, and the grain width of the carbide layer 200 is 1.0-15.0 μm. Compared with the thoriated tungsten filament, the grain size of the carbide layer 200 in the thorium-free filament of the present application is smaller than that of the thoriated tungsten filament, and the grain width is slightly narrower than that of the thoriated tungsten filament. The number of channels 210 in the carbide layer 200 of the present application is more. The organization of the carbide layer 200 at different positions in the filament provided by the present application has a layered block structure organization similar to that formed by the intersection of the first channel 211 and the second channel 212. The first channel 211 is vertically distributed with the edge of the filament, connecting the inside of the substrate 100 and the second channel 212 with the edge of the filament, which is conducive to the outward migration of rare earth atoms and timely replenishment of rare earth elements evaporated from the surface, thereby improving the stability of material emission.

[0412] (2) The initial recrystallization temperature of the filament material provided in the present application is between 48% FC (about 2070°C) and 56% FC (about 2290°C). Therefore, after carburization at a temperature of 2000-2100°C, the grains of the tungsten matrix 100 are relatively fine, and the brittleness of the carburized filament is less than that of the traditional thoriated tungsten filament material, which will reduce the wire breakage rate of customers during production and use.

[0413] (3) The processing performance of the filament material of the present application is better than that of the original thoriated tungsten, the number of flaw detection cracks is less (when the filament wire diameter can reach 500μm, the number of flaw detection cracks of the filament is less than 2 / 100 meters), the processing yield is high, the wound filament is not easy to break, and the production efficiency is improved. In addition, the wire material has fewer cracks, and the proportion of carbonized broken wires in the manufactured filament is also low.

[0414] In the filament material provided by the present application, the oxide of M (such as lanthanum oxide particles) has good plasticity. As the pressure processing proceeds, the oxide particles of M will become thin and long, and exist in linear or quasi-linear shapes; while the thorium oxide in the traditional thoriated tungsten material has poor plasticity. When the thoriated tungsten is processed to a certain extent, the thorium oxide will break. As the processing proceeds further, the thorium oxide will appear as a string of particles; the types of rare earth oxides added in the present application and the changes in morphological structure during the refinement process make the filament material have good processing performance. When preparing wire materials for winding filaments, the wire diameter of the filament material can be refined to 500μm or less, and the number of crack points detected by flaw detection can be effectively reduced, thereby improving the yield rate.

[0415] (4) The thickness of the carbonized layer 200 of the filament of the present application is preferably controlled within a range of 30-90 μm;

[0416] The thickness of the conventional thoriated tungsten filament carbide layer 200 is generally 35-45μm; the thicker the carbide layer 200 is, the longer the service life of the heating device is; however, the conventional thoriated tungsten carbide layer 200 cannot be made thicker, because if the thickness is too large, the recrystallized grains of the tungsten matrix 100 after carbide will be greatly coarsened, making the carbide filament very brittle, and the broken filament ratio in the heating device during production and use will reach 10,000 to 30,000 ppm;

[0417] At present, the thickness of the filament carbonization layer 200 of the embodiment of the present application is also basically 35-50 μm. Unlike the thoriated tungsten filament, the thickness of the carbonization layer of the present application can be thickened, which is conducive to increasing the life. The initial recrystallization temperature of the present application is relatively high, and the tungsten matrix 100 after carburization is still a fine-grained structure, and the filament breakage rate is very low. In this way, the present application can increase the thickness to increase the service life while ensuring that the filament breakage rate remains at a low level, making it possible to thicken the carbonization layer 200.

[0418] (5) The operating temperature of the heating device provided in the present application (i.e., the operating temperature of the filament) can be reduced from 1500-1600°C to 1100-1500°C, such as within the range of 1200-1300°C, and still maintain a good working condition; while the operating temperature of the traditional thoriated tungsten filament is 1600-1900°C. Therefore, the energy consumption and life of the filament provided in the present application and the heating device made therefrom will be improved.

[0419] In summary:

[0420] The filament provided by the present application is prepared by adding one or more oxides and carbides or carbon elements of M into a tungsten matrix 100. The combination of the oxides and carbides or carbon elements can improve the diffusion rate of the material in the matrix 100. Compared with the thorium tungsten filament, the filament can achieve the same or even higher electron emission capability at a lower operating voltage (excitation temperature). At the same time, the grains of the carbide layer 200 are controlled within a certain small size range, and the channel 210 formed on the surface of the carbide layer 200 of the filament is organized to form a layer block. The first channel 211 and the second channel 212 and the edge of the filament are distributed quasi-vertically, which is conducive to the outward migration of rare earth atoms and the timely replenishment of the rare earth elements evaporated from the surface, thereby improving the stability of the material emission. The tungsten alloy filament material provided by the present application replaces the existing thoriated tungsten filament cathode, and has a service life equivalent to or exceeding that of thoriated tungsten. The present application can significantly reduce the initial recrystallization temperature of the material, improve the processing performance of the material, reduce the electron work function of the material, and refine the microstructure grain of the filament by doping M oxide and carbide or carbon element into the tungsten matrix 100 powder. It can reduce the wire breakage rate to reduce the production and transportation costs, and effectively increase the service life of the filament, so that its service life reaches and far exceeds the service life of the existing thoriated tungsten filament.

[0421] The filament provided in the present application can obtain an extremely high recrystallization temperature, and can still obtain extremely fine grains at the same carburization temperature as thoriated tungsten. The material has excellent shock resistance, and can reduce the breakage and failure of the filament during production, transportation and use.

[0422] It should be noted that:

[0423] In this article, “~” is used to indicate a numerical range, and the range indicated by this expression includes two endpoint values;

[0424] In summary, the specific parameters or some commonly used reagents or raw materials in the above embodiments are specific embodiments or preferred embodiments conceived by the present application, but are not intended to limit the present application; those skilled in the art may make adaptive adjustments within the concept and protection scope of the present application.

[0425] It should be noted that the specific parameters or some commonly used reagents in the above embodiments are specific embodiments or preferred embodiments of the present application, rather than limiting the present application; those skilled in the art may make adaptive adjustments within the scope of the present application.

[0426] In addition, unless otherwise specified, the raw materials used may also be conventional commercial products in the art, or may be prepared by conventional methods in the art.

[0427] In addition, those skilled in the art should understand that, although there are many problems in the prior art, each embodiment or technical solution of the present application can be improved in only one or several aspects, without having to solve all the technical problems listed in the prior art or background technology at the same time. Those skilled in the art should understand that the content not mentioned in a claim should not be used as a limitation on the claim.

[0428] Although the terms such as carbonized layer, matrix, channel, etc. are used more frequently in this article, the possibility of using other terms is not excluded. These terms are used only to more conveniently describe and explain the essence of this application; interpreting them as any additional restrictions is contrary to the spirit of this application.

[0429] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A tungsten carbide alloy filament, characterized in that: It includes a substrate and a carbonized layer attached to the outer surface of the substrate; The grain width of the carbonized layer is between 1.0 μm and 15.0 μm; The components of the substrate and the carburized layer both contain tungsten, carbon, oxygen and M; The M element is selected from one or more combinations of La, Y, Sc, Nd, Sm, Lu, Ce, Gd, Tb, Dy, Ho, Pr, Er, Tm, Yb, Eu, Hf, and Zr; Wherein, the components of the tungsten carbide alloy filament do not contain thorium element.

2. The tungsten carbide alloy filament according to claim 1, characterized in that: The M element in the carbonized layer exists in the form of oxide, and the particle size of the M oxide particles is 10nm to 1000nm; the carbon element in the carbonized layer exists in the form of carbide.

3. The tungsten carbide alloy filament according to claim 1, characterized in that: A plurality of second channels are distributed on the carbonized layer, so that a layered structure stacked in a radial direction is formed on the cross section of the filament; A plurality of first channels are distributed on the carbonized layer, and at least part of the first channels are cross-arranged with the second channels, so that the layered structure is divided into a plurality of block structures.

4. The tungsten carbide alloy filament according to claim 1, characterized in that: A plurality of first channels are distributed on the carbonized layer; wherein at least part of the first channels are distributed along the radial direction of the cross section of the filament; and / or at least part of the first channels point to the center of the cross section of the filament; A plurality of second channels are distributed on the carbide layer; at least part of the second channels are distributed along the circumferential direction of the cross section of the tungsten alloy filament; wherein at least part of the second channels are cross-arranged with the first channels.

5. The tungsten carbide alloy filament according to claim 1, characterized in that: The components of the carbonized layer include W2C and WC; the weight ratio of the W2C to the WC is (60-100):(0-40).

6. The tungsten carbide alloy filament according to claim 1, characterized in that: In the matrix, the M element exists in the form of oxide, and the carbon element exists in the form of carbide or carbon element.

7. The tungsten carbide alloy filament according to claim 1, characterized in that: The matrix comprises the following components: 0.0005-0.3 wt% of carbon element, 0.25-2.6 wt% of M element, 0.05-0.5 wt% of oxygen element, and the remainder is tungsten element and inevitable impurities.

8. The tungsten carbide alloy filament according to claim 7, characterized in that: Among the components of the matrix, the M element exists in the form of an oxide, and the carbon element exists in the form of a carbide or a single carbon substance; The oxide of M is selected from one or more combinations of lanthanum oxide, yttrium oxide, scandium oxide, neodymium oxide, samarium oxide, lutetium oxide, cerium oxide, gadolinium oxide, terbium oxide, dysprosium oxide, holmium oxide, praseodymium oxide, erbium oxide, hafnium oxide, and zirconium oxide; The carbide is selected from one or more combinations of lanthanum carbide, zirconium carbide, yttrium carbide, hafnium carbide and tungsten carbide.

9. The tungsten carbide alloy filament according to claim 7, characterized in that: The components of the matrix further include a metal element T; the T is selected from at least one of K, Re, Mo, Fe, and Co.

10. The tungsten carbide alloy filament according to claim 9, characterized in that: The mass content of Re is less than 1000 ppm.

11. The tungsten carbide alloy filament according to claim 1, characterized in that: The wire diameter of the tungsten carbide alloy filament is 800 μm or less.

12. The tungsten carbide alloy filament according to claim 1, characterized in that: The working temperature of the tungsten carbide alloy filament is 1100°C to 1500°C.

13. The tungsten carbide alloy filament according to claim 1, characterized in that: The tungsten carbide alloy filament is a spiral structure, and the thickness of the carbide layer of at least one spiral turn reaches 30 μm to 90 μm.

14. A method for preparing a tungsten carbide alloy filament according to any one of claims 1 to 13, characterized in that: It includes the following steps: Doping and powder making: the finished powder raw material is obtained by sequentially performing the doping process, the reduction process and the powder making process; wherein the doping process is solid-liquid doping or solid-solid doping; Powder pressing: using isostatic pressing to press the finished powder raw material into a compact, and pre-sintering the compact at a low temperature in a hydrogen atmosphere to obtain a pre-sintered blank; High temperature sintering: sintering the pre-sintered billet at high temperature by a high temperature sintering method to obtain a sintered billet; Pressure processing: the sintered billet is processed into a tungsten alloy wire of a certain diameter; wherein, oxidation annealing treatment is performed during the thinning process; Cleaning: cleaning the tungsten alloy wire into tungsten alloy white wire; Winding: Winding the tungsten alloy white wire into a spring-shaped filament structure; Cathode assembly: assembling the spring-shaped filament structure and components, ceramics, and lead parts into a cathode structure through heat treatment; Welding: welding the filament structure in the cathode structure to the component end cap; Carbonization: Carbonizing the welded cathode structure.

15. The method for preparing a tungsten carbide alloy filament according to claim 14, characterized in that: The temperature rise curve of the high temperature sintering step is: From room temperature to A1, the heating time H1 is (5-8) h, A1 is (950-1250) °C; keep warm at A1 for H2 hours, H2 is (1-3); from A1 to A2, the heating time is H3, H3 is (1.5-2.5) h, A2 is (1300-1500) °C; keep warm at A2 for H4 hours, H4 is (2.5-4.5); from A2 to A3, heating time is H5, H5 is (1~3)h, A3 is (1700~1900)℃; keep warm at A3 for H6 hours, H6 is (1~3); heat from A3 to A4, heating time is H7, H7 is (1~3)h, A4 is (2050~2250)℃; keep warm at A4 for H8 hours, H8 is (5~10); cool naturally from A4 to obtain sintered billets; The process of the pressure processing step is: The sintered billet is refined to an intermediate specification wire with a diameter of 1.5 to 3.5 mm; and then the intermediate specification wire is oxidized and annealed at (1200 to 1500)° C. with an annealing speed of (3 to 10) m / min to obtain the tungsten alloy wire.

16. A heating device, characterized in that: It comprises the tungsten carbide alloy filament as described in any one of claims 1 to 13.

Citation Information

Patent Citations

  • Doping method for powder for magnetic control coil

    CN102009179A

  • A non-radiative multi-component composite tungsten cathode material for microwave oven magnetron and its preparation process

    CN103849804B